Structure and characteristics of quercetin-loaded starch nanoparticles and their surface charges for protein corona formation with gastrointestinal digestive enzymes - Yu-Ru Wu; Zhi-Yuan Yang; Shan-Dan Zhao; Dan-Yang Shen; Ya-Jun Lin; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2026)

MiR-324-5p mitigates experimental acute pancreatitis by suppressing Rock2 expression - Qian Chen; Zhao Shen; Qingmei Wang; Ru Jiao; Yehong Liu; Tingting Meng; Yunhui Fei; Caixia Liu (Mammalian Genome, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Polymer-specific oxidative biotransformation of polyethylene and polypropylene microplastics by the stored-grain pest Tribolium castaneum - Sakhawat Shah; Jin-Ru Zhao; Ze-Yu Liu; Yi-Jia Chen; Jie Tang; Karam Khamis Elgizawy; Qiu-Ying Huang; Elvis Genbo Xu; Feng-Lian Yang (Chemical Engineering Journal, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Asymmetric introgression and reticulate evolution result from palaeoclimate-driven range dynamics of the Smilax hispida group in North and Central America - Xin-Yi Fan; Han-Yang Lin; Ya-Lu Ru; Yun-Peng Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

From efficient nitrite accumulation to complete collapse: how a microbial community and its antibiotic resistance genes in a nitrification system respond to long-term exposure to ciprofloxacin and copper - Xiao-Yan Fan; Meng-Hao Hao; Jun-Ru Zhao; Xing Li; Shen-Bin Cao; Jia-Wei Ren; Ding-Chang Li (Journal of Water Process Engineering, 2026)

Mechanisms of typical antibiotic degradation and suppression of resistance gene propagation in a biological manganese oxidation reactor - Huaqing Liu; Xin-Ru Jia; Chong-Yang Ren; Xiaoqiang Cao; He-Ping Zhao; Jian Zhang (Journal of Water Process Engineering, 2026)

Rationally designed aluminum-supported g-C3N4: An efficient and halogen-free catalyst for CO2-epoxide cycloaddition - Man Zhao; Wen-Jun Xie; Shan-Shan Chen; Hong-Ru Li; Liang-Nian He (Journal of Environmental Chemical Engineering, 2026)

Pectin-induced quality improvement of pea protein emulsion template oleogels and their application as fat replacers in sponge cakes - Ru Zhao; Xinxin Yin; Meijun Liu; Guanxin Xie; Yijian Li; Min Zhang; Tiehua Zhang; Haiqing Ye; Cuina Wang (Food Chemistry, 2026)

Recyclable epoxy vitrimers based on multimechanism-activated transesterification strategies for photothermal conversion and self-healing materials - Huanyu Xu; Liangyi Xing; Ru Wang; Guiyu Chu; Yanmeng Peng; Zhiyue Zhao; Fengjiao Jiang; Shuhua Qi; Hongxia Yan (Chemical Engineering Journal, 2026)

pH-responsive microcapsules co-delivering radioprotectant and probiotics for synergistic mitigation of radiation-induced enteritis - Caifang Gao; Jiaxuan Ma; Luke Ge; Yongle Zhao; Ru Feng; Pengqi Zhu; Jinghua Sun; Ruiping Zhang (Chemical Engineering Journal, 2026)

Short-term parental exposure to diazepam disrupts development, behavior, and transcriptional profiles in zebrafish offspring - Qingdong Xu; Yue Xie; Jie Tang; Zhen Su; Kun Chen; Guanghua Mao; Ru-jin Zhao; Yuki Takai; Yohei Shimasaki; Xuchun Qiu (Aquatic Toxicology, 2026)

Antioxidant Activity of Bioactive Peptides Derived from Ulva prolifera in HaCaT Cells and Zebrafish - Li-Ru Hong; Shuo-Qi Wang; Ting-Ting Wu; Zhi-Ru Chen; Mo Chen; Chun-Er Cai; Pei-Min He; Ya Zhao; Rui Jia (Marine Biotechnology, 2026)

Electroacupuncture-induced gut microbiota alterations correlate with FXR/FGF15 activation and metabolic improvement in hyperlipidemic rats - Huan Wu; Li Zhou; Wei Lin; Hong-xing Zhang; Zhao-qing Zhang; Xiao-fei Wang; Shi-ru Ju; Zhi-gang Liu; Fei Hu (Advances in Traditional Medicine, 2026)

Phylogenomics, reticulate evolution, and taxonomic revision of East Asian Cardamine (Brassicaceae) in the Hengduan biodiversity hotspot - Jia-lu Li; Dan-hui Liu; Jiang-lin Miao; Yi He; Liao-cheng Zhao; Di Zhang; Ke-ping Ma; Quan-ru Liu (Molecular Phylogenetics and Evolution, 2026)

On-site rapid detection method for Cryptolestes ferrugineus(Coleoptera: Laemophloeidae) based on recombinase polymerase amplification technology - Zhang Ru; Bai Yueliang; Bai Kaixu; Wang Hongjun; Zhao Chao; Yan Lei; Duangsamorn Suthisut; L.V. Jianhua; Zeng Fangfang; Zhang Meng; Bai Chunqi (Journal of Stored Products Research, 2026)

Microbial and environmental determinants of 1-propanol biosynthesis in Jiang-flavor Baijiu fermentation - Wei-Tao Zhai; Han Zhao; Li-Juan Chai; Wei Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Chuan-Qiang Gao; Guan-Ru Si; Wen-Qing Zhang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Microbiology, 2026)

A macin family antimicrobial peptide from Atrina pectinata exhibiting dual functions in direct bactericidal activity and hemocyte immune modulation - Yan-ru Chen; Kun-yu Zhao; Shun-xin Hu; Ding-long Yang; Xue-peng Li; Li-zhu Chen; Jian-min Zhao (Fish & Shellfish Immunology, 2026)

Diniconazole leads to neurotoxicity in zebrafish via triggering TLR4/MyD88-mediated immune-inflammatory responses - Hongying Zhang; Ru Guo; Youjuan Wu; Jiajun Huang; Zijia Yin; Kaiwen Zhao; Xuefeng Liu; Meifeng Li; Zeyin Jiang; Shanghong Wang; Lihua Fan; Chengyu Hu; et al. (Fish & Shellfish Immunology, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Activation-optimized anti-CD3 valency control enables combinatorial discovery of multi-specific nanoantibodies for solid tumor immunotherapy - Long Zhu; Ya-Jing Ma; Jian-Kang Kang; Xiu-Hai Che; Dong-Kun Zhao; Yin-Yi Cai; Yao-Ru Yu; Song Shen; Jun Wang (Science Bulletin, 2026)

The SP1/NEDD4L Axis Suppresses the Breast Cancer Progression by Downregulating SNAI2 Expression - Baile Zuo; Xiaoyan Li; Mengke Wang; Zhuoya Yin; Yifan Guo; Liping Zhao; Ru Yang; Binghua Tong; Zhenni Guo; Meiqing Sun; Jin Zhao; Huina Zhang; et al. (Biochemical Genetics, 2026)

PdPI, a PISTILLATA ortholog from Populus davidiana, enhances drought tolerance by regulating stomatal aperture and antioxidant defense - Siyuan Li; Meiqi Lu; Ling Jin; Zhanchen Ren; Xinyu Wang; Song Chen; Yunxia Wei; Jiaxin Liu; Yuanfu Liu; Haoran Bao; Yue Zhang; Tingyu Cao; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

FOXG1 Transcriptionally Orchestrates Parvalbumin+ Interneuron Function Contributing to Schizophrenia Pathology - Pengfei Jiang; Mingzhao Su; Xue Zhou; Baoshen Zhang; Jie Sun; Ru Ba; Junhua Liu; Chunjie Zhao (Neuroscience Bulletin, 2026)
Schizophrenia (SCZ) is characterized by heterogeneous symptoms including abnormal perception, social withdrawal, and cognitive deficits. Parvalbumin-positive (PV + ) interneurons are particularly vulnerable in SCZ; however, the underlying cellular basis remains unclear. In this study, we found that selective deletion of the SCZ risk gene Foxg1 in PV + interneurons of mice recapitulated aspects of the disease phenotype, including impaired sensorimotor gating, anxiety-like behavior, social deficits, and cognitive impairments. Foxg1 deficiency caused dendritic simplification, reduced spine density, and impaired synaptic transmission in PV + interneurons of the prelimbic cortex. Our findings indicate that FOXG1 directly drives a set of SCZ risk genes that encode synaptic receptors, adhesion molecules, scaffolding proteins, transporters, ion channels, and vesicle-trafficking proteins, thereby orchestrating PV + interneuron synaptic function. Notably, FOXG1 activates the transcription of metabotropic glutamate receptor 3 (mGluR3), and pharmacological potentiation of mGluR3 activity alleviates behavioral deficits in Foxg1 conditional knockout mice. In conclusion, our findings identify a novel role for Foxg1 in PV + interneurons, providing new mechanistic insights into their vulnerability to SCZ.

Triazine herbicide prometryn impaired trophic link between phytoplankton and zooplankton Brachionus plicatilis by diminishing polyunsaturated fatty acids contents - Wei Liang; Yilei Li; Ziang Zhao; Dongchu Zhao; Yue Wang; Liqiang Yang; Shaoguo Ru; Xiaona Zhang (Marine Pollution Bulletin, 2026)

Coupling microbial electrosynthesis and chain elongation for simultaneous biomethane upgrading and carboxylate recovery: A tunable carbon valorization strategy - Kai-Kai Wu; Shu-tong Wu; Chuan Chen; Zi-Han Wang; Ya-Ru Wang; Li Zhao; Juan Tong; Fei Shen; De-Feng Xing; Nan-Qi Ren; Lei Zhao (Water Research, 2026)

Dual-engineered defect-rich molecularly imprinted zirconium metal organic framework platform for selective adsorption and ultrasensitive analysis of alternariol - Shi-Rong Sun; Lu Liu; Xia Wang; Yan Dong; Yan Li; Qianyun Sun; Yanfang Zhao; Xiangfeng Chen; Yong-Ning Wu; Rabah Boukherroub; Ru-Song Zhao (Journal of Hazardous Materials, 2026)

Study on the Diversity of the CXCL8 Family in Carassius auratus : Homologue Characteristics and Tissue‐Specific Immune Responses Under H. doneci Infection - Jin‐ye Zhang; Hong‐yan Liu; Yue‐ru Wang; Yuan‐jun Zhao (Journal of Fish Diseases, 2026)
Chemokines are essential for vertebrate immune regulation, and teleosts possess diverse CXCL8 lineages. However, studies on CXCL8 in C. auratus remain limited. In the present study, four CXCL8 homologues ( CaCXCL8‐1 to ‐4 ) were successfully cloned and identified from C. auratus , and their expression patterns were analysed in the tissues of healthy and those naturally infected with H. doneci . Bioinformatic analyses revealed that all homologues possess the conserved structural features of CXC chemokines. However, the divergence was observed in the N‐terminal ELR motif: CaCXCL8‐1 and CaCXCL8‐2 harboured a QLR motif, whereas CaCXCL8‐3 and CaCXCL8‐4 possessed a DPR motif. Phylogenetic analysis classified CaCXCL8‐1 and CaCXCL8‐2 into the CXCL8_L2 lineage, and CaCXCL8‐3 and CaCXCL8‐4 into the teleost‐specific CXCL8_L1b lineage. Tertiary structure predictions indicated that CaCXCL8‐1, −3, and −4 conserve key receptor‐binding sites, whereas CaCXCL8‐2 retained only GAG‐binding sites, suggesting potential functional divergence. Under healthy conditions, the four homologues were all constitutively expressed but displayed divergent basal profiles. Following H. doneci infection, they exhibited distinct tissue‐specific expression patterns: CaCXCL8‐1 was significantly upregulated in the gills; CaCXCL8‐2 was specifically induced in the spleen; CaCXCL8‐3 was markedly upregulated in both the gills and head kidney; and CaCXCL8‐4 was upregulated in the liver and head kidney but downregulated in the spleen. These divergent expression patterns suggest functional specialisation among the CaCXCL8 homologues, with different paralogs potentially coordinating localised versus systemic immune responses. Our findings provide evidence for the functional diversification of the CXCL8 chemokine in teleosts and contribute to understanding the evolution of complex immune systems in vertebrates.

Superoxide dismutase/peroxidase-like MoS2 quantum dots enhance ammonia synthesis by Klebsiella pasteurii - Meng-Xin Zhao; Si-Ru Chen; Shan-Shan Hu; Ting-Ting Liu; Jia-Le Teng; Ya-Wen Yu; Jia-Long Zhang; Xue-Ru Zhou; Qun-Feng Ye; Su-Fang Qin; Le-Xing You (Journal of Environmental Chemical Engineering, 2026)

Inhibition effect on swelling and permeability enhancement of potassium benzoate in ion adsorption rare earth ore elution - Ziqi Jin; Yuanlai Xu; Ziqi Wang; Shimin Hu; Junhao Pan; Pei Zhao; Ru'an Chi (Minerals Engineering, 2026)

Emulsion-template oleogels: Formation mechanisms, structural regulation, and potential as solid fat substitutes - Ru Zhao; Min Zhang; Meijun Liu; Xinxin Yin; Guanxin Xie; Haiqing Ye; Tiehua Zhang; Cuina Wang (Food Research International, 2026)

AtGASA1 positively regulates Arabidopsis response to salt stress by suppressing accumulation of reactive oxygen species - Jian-Bo Song; Hao-En He; Cai-Feng Wang; Xian-Zhi Zuo; Zi-Xin Zhao; Ya-Ru Li; Yu-Fan Chen; Shu-Fan Liu; Han-Wen Guo; Xuan Huang (Plant Cell Reports, 2026)

Characterization of a new isolate of tomato zonate spot virus from Vaccinium uliginosum L. in China - Yueyan Yin; Tao Lin; Ru Dong; Zhijiao He; Jing Zhong; Liling Zhao; Jiawei He; Ming Ding; Tingting Li (Journal of Plant Pathology, 2026)

Study of enhancing analgesic potential of μ-conotoxins from the computational and pharmacological insights - Fan Zhao; Yunxia Liu; Ying Cui; Yushan Ding; Liu Ru; Ting Meng; Hongtao Yang; Yongbo Song (Molecular Diversity, 2026)

The unique biogenesis pathway of extracellular vesicles in Hirudo nipponia salivary gland cells - Ya-Li Zhu; Meng-Xiang Jia; Ru-Yu Qu; Qian Li; Xia Qiu; Wen-Chen Zhao; Yuan-Yuan Luo (Tissue and Cell, 2026)

Editor's note “Silica nanoparticles promoted pro-inflammatory macrophage and foam cell transformation via ROS/PPAR/NF-B signaling” [Sci. Total Enviro. 881 (2023) 163430] - Caixia Guo; Xinying Zhao; Ru Ma; Lingnan Zhu; Yueyue Chen; Zhiwei Sun; Yanbo Li (Science of The Total Environment, 2026)

Mechanochemistry synthesis of Al-fumarate MOF towards high-performance in solar-driven interfacial water evaporation and electricity generation - Jun Liu; Ruiqi Li; Guixin Hu; Nan Yao; Juan He; Ru Tao; Tingting Jia; Li Lu; Liping Zhao; Jiang Gong (Journal of Environmental Chemical Engineering, 2026)

Identification of key factors influencing monthly runoff simulation through the integration of deep learning and physically-based hydrological models - Jiyu Zhang; Yufeng Wang; Liangjie Zhao; Ru Sun; Jiayu Sun; Shufei Wang; Shiqin Xu; Zhe Yang (Environmental Modelling & Software, 2026)

Highly sensitive ppb-level high-entropy metal oxide gas sensor with temperature-dependent dual-selectivity for Ammonia and Triethylamine - Ru Wang; Guozheng Zhu; Yutong Guo; Yilin Du; Mengran Ran; Yuxin Cao; Hongmin Zhu; Fanli Meng; Yong Zhao (Chemical Engineering Journal, 2026)

Efficient Biosynthesis of Selenium-Enriched Saccharomyces cerevisiae via Siderophore-Assisted selenite uptake and biotransformation - Wen-tao Du; Ya-ru Wei; Xue Zhao; Qiang-qiang Gou; Omer Hassan Ali; Wen-di Wang; Jia-nan Xu; Zai-ping Feng; Xin-guo Zhang (Bioresource Technology, 2026)

Size Effects on Backfill–Rock Interface Shear Behavior: Insights from Multi-method Modeling - Wenkai Ru; Jinyin Ma; Hiroyuki Noda; Diyuan Li; Hao Gong; Junjie Zhao; Zhen Li (Rock Mechanics and Rock Engineering, 2026)

Immobilization and magnetic removal of lead in contaminated soils using a waste-derived magnetic molecular sieve - Chang Lei; Xiu-Ru Xie; Lai-Shou Long; Rui Li; Zhi-Ping Fu; Zhi-Yue Zhao (Journal of Soils and Sediments, 2026)

Uncertainty quantification of the hardening soil model - Bangxiang Li; Youliang Zhang; Zhongliang Ru; Hao Liu; Zhiqing Wang; Hongbo Zhao (Bulletin of Engineering Geology and the Environment, 2026)

Studies on secondary metabolites and anti-inflammatory activity of fungus Penicillium citreosulfuratum YFC-1 from Sphagneticola trilobata - Zhao-xia Chen; Wen-xing Li; Ru-tong Chen; Yang Hui; Zhen-fan Sun; Wen-hao Chen (Natural Product Research, 2026)

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Microplastic-pathogen interactions differentially modulate tomato Fusarium wilt severity: The dependence of polymer biodegradability - Siqi Shen; Yawei Zhou; Ru Zhao; Meng Liu; Wenjiang Fu; Shuting Zhao; Chaokai Yan; Qi Gao; Dan Zhang; Yanhua Wang; Hanzhong Jia; Yahong Wei (Journal of Hazardous Materials, 2026)

Mechanism of the influence of single-phase dynamic gelation process on the structure and properties of bigels - Yanlei Gao; Qing Xiong; Shilin Zhao; Qilin Huang; Yang Hu; Ru Liu (Food Hydrocolloids, 2026)

Mechanism of adsorption and biodegradation of typical antibiotics by sediments in mariculture tailwater system - Jun-Ru Zhao; Xing Li; Yan-Ling Yang; Zhi-Wei Zhou; Ze-Dong Lu; Xiao-Yan Fan (Environmental Research, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

Synergistic activation of the bioenergetics-apoptosis axis via flavonoids-loaded cascade-targeted biomimetic nanoplatform to overcome cancer metabolic plasticity - Xue Zheng; Yunfan Shao; Xue Gao; Yu Hao; Yanhui Shi; Ru Xie; Miaoqing Zhao (Chemical Engineering Journal, 2026)

Potassium ferrate-coupled endogenous free ammonia enhancing volatile fatty acids production in anaerobic fermentation of concentrated sludge: Insights into efficiency and mechanisms - Qianqian Wang; Xinyu Zhao; Ru Zhang; Yaoxian Hu; Yuping Ye; Wei Fang; Panyue Zhang; Guangming Zhang (Chemical Engineering Journal, 2026)

Real-time visualization of Nocardia seriolae proliferation and macrophage migration in the Northern snakehead (Channa argus) - Jian Teng; Jian-Ru Liu; Yi-Xiang Zhai; Sheng-Liang Cao; Zhen-Shu Si; Qing-Teng Ren; Xiang-Shan Ji; Mei-Hua Lu; Yu-Bao Li; Yan Zhao (Aquaculture, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Naphthalene versus benzene donor in vinyl-linked donor–π–acceptor COFs: Dueling for photocatalytic H2O2 production and water purification - Tong Chen; Meng Xie; Wenli Wu; Xiangfeng Chen; Lingxi Zhao; Ru-Song Zhao (Chemical Engineering Journal, 2026)

Side-chain modified covalent organic frameworks for enhanced visible light photocatalytic degradation of bisphenol A and application in seawater - Tianshuo Liu; Jing Sun; Meng Xie; Ru-Song Zhao (Chemical Engineering Journal, 2026)

Microbial functional shifts drive soil phosphorus transformation under long-term nitrogen and water inputs in a semi-arid grassland - Mohsin Mahmood; Ru Tian; Yan Shen; Jiatao Zhang; Lan Du; Anam Ayyoub; Ansa Rebi; Adnan Mustafa; Haoyue Chen; Yiming Zhao; Wenhuai Li; Le Qi; et al. (CATENA, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Anti-diabetic properties of yellowfin tuna protein hydrolysates and identification and screening of novel anti-diabetic peptides against α-amylase and DPP-IV - Xiangtan Zhao; Peng Wan; Deke Chen; Bingna Cai; Hua Chen; Jun Li; Si Li; Ailing Duan; Ru Li; Si Zhang; Jianyu Pan (Food Chemistry, 2026)

Built-in electric field and surface adsorption enhanced gas detection of muti-interface MXene/TiO2/Bi2MoO6 integrated heterostructure - Yan Liang; Peipei Yan; Xiaojian Zhao; Chunbo Ru; Lu Tang; Yu Jiang; Yong Yang (Chemical Engineering Journal, 2026)

Microbial-electrochemical driven simultaneous biogas upgrading and high-value medium-chain carboxylic acid production - Ya-Ru Wang; Chuan Chen; Shu-Tong Wu; Zi-Han Wang; Lei Zhao; Juan Tong; Kai-Kai Wu; De-Feng Xing; Ai-Jie Wang; Nan-Qi Ren (Bioresource Technology, 2026)

Continuous Removal of Fluoride by Fe/Al-Anchored Bamboo Charcoal in Fixed Bed Column and Prediction of Breakthrough Curve using Artificial Neural Network Model - Shuqin Bai; Ru Ya; Wei Ding; Xiaohua Xie; Mingjun Zhou; Guojing Zhao; Tianxu Yang (Water, Air, & Soil Pollution, 2026)

Hematopoietic Growth Factors Induce More Extensive Transcriptomic Remodeling in Cerebral Monocytes/Macrophages than in Microglia During the Chronic Phase of Traumatic Brain Injury - Sushil Gaire; Robert S. Gardner; Michele Kyle; Xuecheng Qiu; William Miller; Lawrence S. Chin; Li-Ru Zhao (Molecular Neurobiology, 2026)

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

7,8-Dihydroxyflavone attenuates cisplatin-induced cardiomyocyte apoptosis and mitochondrial dysfunction via the p53/Nrf2 pathway - Zhen Tian; Ting-ting Tan; Yu-wei Hu; Jia-tong Yao; Xiao-ting Kang; Jin-yu Zhou; Dong-xu Jia; Qing-liu Li; Ru-jin Liang; Li-mei Zhao; Hua Zhu; Jing Zhao; et al. (Toxicology and Applied Pharmacology, 2025)

Assessing the atmospheric deposition of inorganic nitrogen and phosphorus over the Yellow Sea - Limin Yu; Ru Li; Chong Zhang; Hao Sun; Zhe Zhang; Pengfei Zhao; Pengji Zhang; Fan Yang (Regional Studies in Marine Science, 2025)

Characterization and risk prioritization of PFAS via nontarget screening in soil and maize near a fluoropolymer manufacturing facility - Xiaotong Li; Na Li; Ru-song Zhao; Yali Shi; Yaqi Cai (Journal of Hazardous Materials, 2025)

Fluoride species conversion-enhanced selective extraction: A green and safe strategy for fluorine recovery in wet-process phosphoric acid production - Long Yao; Guixuan Shan; Abrar Laiba; Yu Zhao; Yujiao Zhang; Ru’an Chi; Bingwen Long; Wei Li; Jinli Zhang (Journal of Environmental Chemical Engineering, 2025)

High efficient protein recovery from surimi rinsing wastewater by coupling isoelectric and electrophoretic effects in an electric field - Shilin Zhao; Jiani Zhang; Yanlei Gao; Shanbai Xiong; Juan You; Tao Yin; Ru Liu (Innovative Food Science & Emerging Technologies, 2025)

Antibiotics, antibiotic resistance genes, and environmental drivers: Assessment of resistance pollution along the Yangtze River Basin - Chengcheng Bu; Chong Chen; Weiwei Zhang; Ru Zhang; Jinpeng Yu; Yu Hua; Haoyu Zeng; Yuchen Han; Ruolan Jia; Qihui Zhao; Yuefei Ruan; Limin Ma (Environmental Pollution, 2025)

Correction: Combining network Pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Combining network pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Single-cell RNA sequencing of neonatal cortical astrocytes reveals versatile cell clusters during astrocyte-neuron conversion - Jiaxue Cha; Peng Zeng; Hui Zong; Jiayi Zhao; Jiayao Chen; Haowei Zuo; Bowen Zhang; Changjie Shi; Jing Li; Qiuhong Hua; Zixin Wang; Yujun Hou; et al. (Molecular Biology Reports, 2025)

Balanced Source-Sink Strength in Optimized Cultivation Management of Wheat Could Coordinate High Yield and High Nitrogen Use Efficiency - Juan Kang; Yingying Chu; Jiaxin Zhao; Geng Ma; Haiyan Zhang; Yanfei Zhang; Guozhang Kang; Guangxin Ru; Dongyun Ma; Yingxin Xie; Chenyang Wang (International Journal of Plant Production, 2025)

Identification of the Q-type ZFP gene family in Triticeaes and drought stress expression analysis in common wheat - Pengyan Guo; Changyan Cui; Baoquan Quan; Jiping Zhao; Jingna Ru; Yanzhen Wang; Zhiyuan Song; Aohui Lin; Shuwen He; Guanghao Wang (Genetica, 2025)

The function of salt responsive promoter of Suaeda salsa SsCLCb explains why the species can accumulate large amount of nitrate from saline soils - Chenyang Li; Runtai Zhao; Ru Liu; Ruiqi Zhang; Xiaolei Yang; Chaoran Shi; Lei Wang; Jie Song (Marine Pollution Bulletin, 2025)

Alteration in conformation and emulsibility of lactoferrin-low methoxyl pectin complexes induced by non-covalent interactions with rosmarinic acid - Chuanrui Jiang; Fujun Liu; Yuxin He; Ru Zhao; Chao Dong; Tiehua Zhang; Cuina Wang (Food Chemistry, 2025)

Effects of EGCG/TGase on the physicochemical properties and in vitro dynamic digestion characteristics of water-saving rinsed surimi gels - Qin Yang; Weixia Zhou; Die Hu; Chuan Li; Lu Zhang; Yongqiang Zhao; Shengbi Zou; Ru Liu; Youming Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Insights into the synergistic cross-linking effect of EGCG and TGase on surimi gels - Qin Yang; Jinling Li; Wentao Ma; Ru Liu; Shengbi Zou; Yongqiang Zhao; Shanbai Xiong; Jianhua Rong; Yang Hu (Food Chemistry, 2025)

Ionic liquids accelerate the crystallization of a magnetic fluorine-functionalized 3D covalent organic framework for efficient capture of trace benzoylurea insecticides in juices and beverages - Zekun Liu; Lu Liu; Yan Dong; Yan Li; Chong Zhang; Xiao-Li Wang; Lingxi Zhao; Hai-Long Jiang; Yong-Ning Wu; Xiangfeng Chen; Feng Li; Ru-Song Zhao (Chemical Engineering Journal, 2025)

Particulate pollution in underground restaurants with increased use of prefabricated dishes: Characteristics and influential factors - Yiyun Zhuang; Almira Anwar; Zhe Li; Ru Zhang; Feng Shi; Yuehua Lin; Chen Chen; Bin Zhao (Building and Environment, 2025)

Modeling Dress-Out Traits Based on Morphological Traits in the Siberian Prawn, Exopalaemon modestus (Heller, 1862) - Liangjie Zhao; Zhiguo Hu; Congying Duan; Ru Zhang; Jiahui Liu; Xusheng Guo (Fishes, 2025)
Dress-out traits, such as abdominal meat weight and abdominal meat percentage, are difficult to improve through direct selection in aquatic species due to the lack of reliable measurement methods. To facilitate the prediction of these traits from morphological characteristics in live prawn, Exopalaemon modestus, a total of 518 individuals were collected in 2025 from Suyahu Reservoir in the upper Huaihe River, China. After excluding individuals with incomplete appendages and egg-bearing females, 301 prawns were randomly selected for model development, and the remaining 60 were used for validation. Based on integrated grey relational analysis and path analysis, body mass was identified as the most effective predictor of abdominal meat weight (p

Inhibition of the NLR pathway alleviates MAPK1 mutation-driven proliferation and differentiation deficits and enhanced apoptosis in P19 cells - Tingying Lei; Lei Liu; Fei Guo; Ru Li; Li Zhen; Fang Fu; Min Pan; Jin Han; Hang Zhou; Chunling Ma; Ruibin Huang; Xinyi Zhao; et al. (Tissue and Cell, 2025)

Porous Janus membrane for ultrasensitive detection and efficient degradation of sulfur mustard simulant - Meiyang Jin; Shuya Liu; Hailong Jiang; Xia Wang; Yongxian Guo; Yanjun Gong; Qiongzheng Hu; Ru-Song Zhao (Journal of Hazardous Materials, 2025)

Analysis of the synchronous enhancement in CO2 sequestration by steel slag using steam in flue gas: performance and mechanism - Shuang Wang; Yi-fei Zhang; Kai Zhao; Hong-ming Long; Ru-fei Wei (Journal of Cleaner Production, 2025)

Effect on the characteristics of biofilm and activated sludge of different COD/TN in H-MABR reactor - Shizhang Wu; Xiaolin Li; Xing Zheng; Pengyu Zhuang; Chi Zhang; Qiujin Ru; Tong Liu; Kun Zhang; Xiaoguang Zhao; Guan Wang; Mingyang Qi; Xiaoliang Li (Journal of Environmental Chemical Engineering, 2025)

Fabrication of self-supported amorphous layered double hydroxides/bamboo biochar electrode for boosting its performance as symmetric supercapacitors - Zhuo Wang; Xiao Li; Qing Cai; Zhao-Yang Pan; Li Li; Yuan-Ru Guo; Qing-Jiang Pan (Chemical Engineering Journal, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

A scientific data-driven review of natural product genipin for disease therapy - Dong Xu; Tao Qiao; Kai Gao; Mei-Na Zhao; Wei Zhang; Xing-Ru Tao; Jing-Wen Wang (Phytochemistry Reviews, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Green manure roots return drives saline-alkali soil organic carbon accumulation via microbial necromass formation - Fangdi Chang; Hongyuan Zhang; Peiyi Zhao; Na Zhao; Jiashen Song; Ru Yu; Jing Wang; Xiquan Wang; Dongxun Han; Xiaodong Liu; Jie Zhou; Yuyi Li (Soil and Tillage Research, 2025)

STING inhibition suppresses butachlor-induced splenic macrophage pyroptosis and M1 polarization via cGAS-STING signaling - Ru-Yang Zhao; Mu-Zi Li; Qi-Qian Wang; Fu-Wei Jiang; Yi Zhao; Jin-Long Li (Journal of Hazardous Materials, 2025)

FlexiSAM: A flexible SAM-based semantic segmentation model for land cover classification using high-resolution multimodal remote sensing imagery - Zhan Zhang; Daoyu Shu; Cunyi Liao; Chengzhi Liu; Yuanxin Zhao; Ru Wang; Xiao Huang; Mi Zhang; Jianya Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Comparison of hydroxylated flavonoids and their interaction with protein-based carriers - Zhi-Yuan Yang; Shan-Dan Zhao; Yu-Ru Wu; Qian Zhou; Wei Wang; Yi-Bin Zhou; Kang Liu (Food Chemistry, 2025)

Multispectral analysis and molecular docking simulation of the inhibition mechanism of dietary anthocyanins on acetylcholinesterase - Nuo Wang; Min Zhao; Yue Li; Hao-Yu Xue; Xu Si; Chi Shu; Ying Zhou; Bao-Ru Yang; Sergey S. Makarov; Anton I. Chudetsky; Liang Wang; Ying He; et al. (Food Bioscience, 2025)

Covalent binding of vitamin K3 photosensitizers to nanofibrous membranes for daylight-driven antimicrobial applications - Yibo Ru; Qingli Dong; Kexin Li; Xinyi Zhao; Lang Yan; Xiang Wang; Yangtai Liu; Yue Ma (Chemical Engineering Journal, 2025)

Electrocatalytic synergistic degradation of tetracycline by low-energy-consumption Mn0.22-NiS nanosheet electrodes: Interface mechanism and toxicity analysis - Fan-Hao Hu; Qun-Feng Ye; Si-Ru Chen; Ya-Wen Yu; Hao Chen; Su-Fang Qin; Le-Xing You; Xiao-Chun Tian; Feng Zhao (Chemical Engineering Journal, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Anaerobic Digestion Enhances the Comprehensive Utilization of Shaddock Peel: Methane Production, Biochar Preparation, and CO2 Capture - Chengcheng Cao; Ru Li; Huantao Dai; Yan Zhao; Ling Sun; Xinheng Zhuang; Xueyang Zhang (Water, Air, & Soil Pollution, 2025)

Transcriptome Profiling of the Primary and Crown Root in Response to Nitrate in Foxtail Millet (Setaria italica) - Xueting Kang; Jian-Hong Hao; Jiayi Chen; Xuan Zhou; Dan-Ying Chen; Rui Zhao; Ru Meng; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; et al. (Journal of Plant Growth Regulation, 2025)

Efficient Microbial Production of Selenium Nanoparticles by Selenium-Tolerant Alcaligenes sp. HZ-9-3-3 - Omer Hassan Ali Hassan; Ya-Ru Wei; Zai-Ping Feng; Jia-Mei Pei; Jia-Nan Xu; Wen-Tao Du; Qiang-qiang Gou; Wen-Di Wang; Xue Zhao; Qin-Cui Shi; Xin-Guo Zhang (Current Microbiology, 2025)

Architectural features and antioxidative biofunctionality of a novel pectin from Angelica keiskei Koidz - Si-Ru Chen; Yu-Ru Zhu; Li-Ting He; Hong-Liang Sun; Jing Huang; Yan-Zi Yang; Hua-Jun Zhao; Bo Yang; Meng-Xia Yan (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

Efficient removal of dissolved tri-n-butyl phosphate from aqueous solution by immobilized bacterial microspheres - Si-Yi Ren; Zhao-Xing Peng; Jin-Ru Feng; Xi-Ming Zeng; Hong-Gang Ni (Journal of Environmental Management, 2025)

Responses of coastal phytoplankton communities to herbicide exposure: enhanced resistance coupled with reduced resilience - Yunsheng Wang; Ziang Zhao; Xiukai Song; Xiangyang Jiang; Jiuqiang Xiong; Shaoguo Ru; Liqiang Yang (Environmental Research, 2025)

Nepenthes-inspired liquid-infused membranes with capillary-enhanced thermal efficiency anti-scaling, and anti-fouling for direct contact membrane distillation - Rishun Li; Ru Liu; Volker Abetz; Lizhi Zhao; Zhenzhen Zhang; Xiaoniu Yang (Chemical Engineering Journal, 2025)

Phylogenomics provides new insight into the phylogeny and diversification of Asian Lappula (Boraginaceae) - Dan-Hui Liu; Quan-Ru Liu; Komiljon Sh. Tojibaev; Alexander P. Sukhorukov; Hafiz Muhammad Wariss; Yue Zhao; Lei Yang; Wen-Jun Li (Molecular Phylogenetics and Evolution, 2025)

Transfer patterns of human blood to follicular fluid of per- and polyfluoroalkyl substances with distinct molecular structures and physico-chemical properties - Yun-Ting Zhang; Michael S. Bloom; Yang Zhou; Saif Ur Rehman; Chu Chu; Kun Zhao; Biao Yin; Zhong Lin; Yuan-Yuan Fan; Li-Zi Lin; Ru-Qing Liu; Weihong Tan; et al. (Journal of Hazardous Materials, 2025)

The effects of the 2D aligned fibers on the fracture properties of steel fiber reinforced cementitious composite slab: Simulation and experimental validation - Kelai Yu; Yu Hu; Ru Mu; Peng Xing; Nan Zhao; Longbang Qing (Engineering Structures, 2025)

Engineering an Ag2Se@PANi core–shell nanozymes – Klebsiella pasteurii hybrid system with enhanced ammonia synthesis - Meng-Xin Zhao; Si-Ru Chen; Bo Hu; Hao Chen; Ya-Xuan Xiao; Ting-Ting Liu; Shan-Shan Hu; Su-Fang Qin; Xuee Wu; Le-Xing You; Feng Zhao (Bioresource Technology, 2025)

Indoor and outdoor bioaerosol distributions and concentration profiles during different seasons and pollution events in Qingdao city - Ru Zhao; Liang Guo; Jianhua Qi; Taicheng An (Building and Environment, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Spatial distribution changes and habitat conservation of medicinal plant diversity in the Yinshan Mountains (China) under climate change - Zeyuan Zhao; Yaqiong Bi; Xinxin Wei; Yuan Chen; Ru Zhang; Jingxia Guo; Mingxu Zhang; Xiaobo Zhang; Minhui Li (Journal of Geographical Sciences, 2025)

Mitoquinone mesylate promotes oocyte maturation and subsequent embryonic development by regulating oxidative stress in Tibetan sheep - Bozhen Ji; Chengtu Zhang; Ruolin Zhao; Yifan Pan; Hong Wu; Yongzhong Chen; Ying Wu; Ru Meng; Yingbing Zhang; Yujie Tang; Jianmin Su (Animal Reproduction Science, 2025)

Climate change, social environment, health, and urban inequality: Developing a novel adaptive evaluation framework - Nan Jia; Yinshuai Li; Zhimeng Jiang; Rongfei Su; Xin Lan; Kai Zhang; Wen Song; Rui Zhao; Zilong Xia; Yongze Song; Zehua Zhang; Mengting Wang; et al. (Sustainable Cities and Society, 2025)

Experimental evidence for viral impact on microbial community, nitrification, and denitrification in an agriculture soil - Hu Li; Sha Zhao; Meng-Ke Gao; Yanyan Zhou; Bo Xu; Le-Yang Yang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2025)

Fabrication, characterization, and application in 3D printing of high internal phase emulsion stabilized by alkaline thermal treated pea protein and pectin complex - Ru Zhao; Boxue Xia; Abbas Khan; Yanjiao Chang; Xin Guo; Yaxuan Liu; Xin Huang; Cuina Wang (Food Research International, 2025)

Structural evaluation and formation regularities of garlic clove-like meat in prefabricated grass carp - Qin Yang; Junhong Xie; Yuting Zhang; Yiling Tian; Liang Song; Yongqiang Zhao; Jian Xiong; Ru Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Effects of combined exposure to polyethylene and oxidized polycyclic aromatic hydrocarbons on growth, development, and neurobehavior in Zebrafish - Yu Liu; Yujun Ning; Yi Jiang; Yiquan Ou; Xiaobing Chen; Chiting Zhong; Ru Wang; Zhibo Zhang; Kongfan Wang; Dingxin Long; Weichao Zhao (Aquatic Toxicology, 2025)

Recent duplications and rare structural variations revealed by comparative sequence analysis of low molecular weight glutenin subunits (LMW-GS) genes re-identified using LMWgsFinder in 26 genomes of the grass family - Shengli Zhang; Xiaojing Shan; Yun Wang; Tairui Lu; Daxing Xu; Han Gong; Yuchao Fan; Yuanyuan Guan; Junjie Zhao; Haili Sun; Dongfang Li; Haiyan Hu; et al. (Theoretical and Applied Genetics, 2025)

Asymbiotic Nitrogen Fixation in the Phyllosphere of Urban Green Spaces - Jian-Feng Li; Le-Yang Yang; Zhao Zhang; Xin-Rong Huang; Hu Li; Shun Li; Xiao-Ru Yang (Current Microbiology, 2025)

Flotation separation of parisite from calcium-bearing gangue minerals using polyaspartic acid as a depressant - Jingyang Shi; Jing Lv; Jieliang Wang; Zhao Cao; Wenda Lu; Yongdan Cao; Xu Wu; Xiaoping Wang; Jiayan Tang; Zhenyue Zhang; Ru-an Chi (Minerals Engineering, 2025)

Impact of typhoon on nutrient contaminants, antibiotic resistance genes and microbial communities in mariculture tailwater treatment system - Jun-Ru Zhao; Xing Li; Yan-Ling Yang; Xiao-Yan Fan (Environmental Research, 2025)

Chlorinated paraffins exposure in particulate matter increase the risk of attention-deficit/hyperactivity disorder symptoms in children and adolescents - Wan-Ting He; Jing-Wen Huang; Yun-Ting Zhang; Edwin Trevathan; Zhengmin Qian; Ri'enna Boyd; Michael Elliott; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Guang-Hui Dong (Environmental Pollution, 2025)

Spatially confined Co nanoparticles in N doped carbon material for high efficiency capacitive deionization - Jianwei Wu; Yuzudi Tong; Xinhua Huang; Dongyin Qin; Ruikun Zhao; Ru Li; Guangzhi Hu (Desalination, 2025)

Role of earthworms and their excretion products in reducing antimicrobial resistance and putative pathogens during vermicomposting - Ning Liu; David W. Graham; Yi Zhao; Xiao-Ru Yang; Gang Li; Yong-Guan Zhu (Chemical Engineering Journal, 2025)

Ribosomal protein S3A (RPS3A), as a transcription regulator of colony-stimulating factor 1 (CSF1), promotes glioma progression through regulating the recruitment and autophagy-mediated M2 polarization of tumor-associated macrophages - Liang Zhang; Kun Wang; Fei Li; Lingxue Zhang; Lin Wu; Ru Tie; Kamulan Litifu; Yujie Fu; Simeng Liu; Jiaxin Ni; Pan Chang; Jun Xu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Molecular mechanisms of ascorbic acid affected by ozone in fresh-cut kiwifruit: Insights from salicylic acid synthesis and signal transduction - Yajing Wang; Jingxuan Ma; Tianyu Wang; Liyan Rong; Yingqi Zhao; Shuyue Zhang; Zixuan Liu; Ru Wang; Zhaoxia Wu (Postharvest Biology and Technology, 2025)

Enzymatic degradation of Ochratoxin A by a novel bacterium, Microbacterium esteraromaticum ASAG1016 - Ru Jia; Jingyi Zhao; Senmiao Tian; Faizan Ahmed Sadiq; Simeng Lu; Pengyan Gao; Guohua Zhang (International Journal of Food Microbiology, 2025)

Designing multilayer interlocked architectures with vertical LDH nanosheets in ZIF-67 composite membranes for upgrading CO2 separation - Yan-Mei Zhang; Li-Hao Xu; Xiao-Xue Hu; Bing-Hong Chen; Xin-Ru Chen; Qian-Qian Li; Heng Mao; Zhi-Ping Zhao (Chemical Engineering Journal, 2025)

Metal-organic coordinated self-assembled nanomedicine for enhanced cuproptosis-mediated chemo-photo-chemodynamic synergistic therapy of non-small cell lung cancer - Ru-Gui Liu; Rui-Rui Zhao; Zi-Wei Yu; Feng-Juan Liu; Chun-Zhao Liu; Xiao Wu (Chemical Engineering Journal, 2025)

Co-occurrence of mcr-9 and blaNDM-5 in Multidrug-Resistant Enterobacter hormaechei Strain Isolated from a Patient with Bloodstream Infection - Ru Li; Junfeng Wang; Weiting Zhang; Chenhao Zhao; Mingxiao Han; Hong Du; Haifang Zhang (Current Microbiology, 2025)

Location optimization of unmanned aerial vehicle (UAV) drone port for coastal zone management: The case of Guangdong coastal zone in China - Jia Sun; Sijing Shu; Hongda Hu; Yingbin Deng; Zhao Li; Shengnan Zhou; Yue Liu; Minwen Dang; Wumeng Huang; Zhiwei Hou; Xiaoling Yin; Ru Zhang; et al. (Ocean & Coastal Management, 2025)

Facile preparation of hydrophobic covalent organic framework-coated sponge for efficient oil/water separation - Xiang Lai; Quanmei Duan; Chang Ru; Xin Zhang; Hui Zhao; Can-Peng Li (Journal of Water Process Engineering, 2025)

Efficient fluconazole degradation by activating peroxymonosulfate with LDH-coated nickel foam: Synergism of radical and non-radical pathways - Xiang-Yang Li; Ling-Xi Zhao; Meng Xie; Ning Liu; Xiang-Feng Chen; Ru-Song Zhao (Journal of Water Process Engineering, 2025)

Multiomics unraveled that gibberellin signaling underlies adaptation of rice to ciprofloxacin stress: Calling for concerns on the adverse effects of pharmaceutical residues in water during agricultural irrigations - Xin Qi; Rui Zhao; Xiaona Zhang; Shaoguo Ru; Jiu-Qiang Xiong (Journal of Hazardous Materials, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Efficient adsorption behavior of Fe-based ternary magnetic LDHs for naphthalene acetic acid: Role of Fe element - Ning Liu; Ti-Bo Fang; Ling-Xi Zhao; Na Li; Xiang-Feng Chen; Ru-Song Zhao (Environmental Research, 2025)

Plug-and-play DISep: Separating dense instances for scene-to-pixel weakly-supervised change detection in high-resolution remote sensing images - Zhenghui Zhao; Chen Wu; Lixiang Ru; Di Wang; Hongruixuan Chen; Cuiqun Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Effect of vacuum frying on the structure and bioactivity of proanthocyanidins in Chinese quince (Chaenomeles sinensis Koehne) fruit - Yu Lou; Xu Fang; Zi-Cheng Yang; Jia-Lin Fei; Yu-Ru Feng; Zhao Qin; Hua-Min Liu; Yu-Xiang Ma; Xue-De Wang (Food Chemistry, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

Fast simulation strategy for capacitively-coupled plasmas based on fluid model - Jing-Ze Li; Ming-Liang Zhao; Yu-Ru Zhang; Fei Gao; You-Nian Wang (Computer Physics Communications, 2025)

Astragalus polysaccharide/carboxymethyl chitosan/sodium alginate based electroconductive hydrogels for diabetic wound healing and muscle function assessment - Letian Tang; Shuyang Xie; Danyang Wang; Yiying Wei; Xiaopu Ji; Yicheng Wang; Nana Zhao; Zonglei Mou; Baoping Li; Wan Ru Sun; Ping Yu Wang; Nicola Paccione Basmadji; et al. (Carbohydrate Polymers, 2025)

Impact of carbon/nitrogen ratio on sequencing batch biofilm reactors initiated with different seed sludges for treating actual mariculture effluents - Xiao-Yan Fan; Shi-Long Zhou; Yanling Yang; Shen-Bin Cao; Yue Niu; Meng-Yuan Zheng; Jun-Ru Zhao (Bioresource Technology, 2025)

Tetrachlorantraniliprole induces neurodevelopmental toxicity through oxidative stress-mediated apoptosis and dysregulation of Wnt signaling pathway - Ru Guo; Youjuan Wu; Tingting Yu; Chen Guo; Zijia Yin; Guannan Zhao; Meifeng Li; Huiling Mao; Chengyu Hu; Xiaowen Xu (Aquatic Toxicology, 2025)

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

Self-driven electrochemical system for struvite and energy recovery from digested wastewater: Device optimization strategy and long-term operation - Yi-fan Niu; Ting-ting Dong; Zhi-guo Zhao; Meng-Yu Liu; Ru Wang; Lin-jiang Yuan (Journal of Environmental Management, 2025)

Effects of mixing ratio on physicochemical, structural properties and application in lycopene-loaded emulsions of blends of whey protein and pea protein - Ru Zhao; Chuyu Chang; Yuxin He; Chuanrui Jiang; Zhaoxue Bao; Cuina Wang (Food Chemistry, 2025)

The Interplay Between Accumulation of Amyloid-Beta and Tau Proteins, PANoptosis, and Inflammation in Alzheimer’s Disease - Xianbo Zhuang; Jie Lin; Yamin Song; Ru Ban; Xin Zhao; Zhangyong Xia; Zheng Wang; Guifeng Zhang (NeuroMolecular Medicine, 2024)

Amorphous Solid Dispersions of Glycyrrhetinic Acid: Using Soluplus, PVP, and PVPVA as the Polymer Matrix to Enhance Solubility, Bioavailability, and Stability - Meng-yu Zhao; Xian-bao Shi; Jin-hua Chang; Ru-xing Wang; Jian-yu Zhou; Pei Liu (AAPS PharmSciTech, 2024)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Physical properties and antioxidant activity of curcumin‑zinc metal-organic frameworks - Li-Hang Chen; Tao Chen; Ru-Nan Zhao; Di Wu; Yi-Nan Du; Jiang-Ning Hu (Food Chemistry, 2024)

Zebrafish FKBP5 facilitates apoptosis and SVCV propagation by suppressing NF-κB signaling pathway - Zijia Yin; Hongying Zhang; Kaiwen Zhao; Yulong Liu; Ru Guo; Pengxia Xu; Guannan Zhao; Menglei Hu; Chengyu Hu; Xiaowen Xu (Fish & Shellfish Immunology, 2024)

Cell-permeable PI3 kinase competitive peptide inhibits KIT mutant mediated tumorigenesis of gastrointestinal stromal tumor (GIST) - Zongying Jiang; Yue Guo; Jun Shi; Shaoting Zhang; Liangying Zhang; Yapeng Wang; Guofu Li; Ru Bai; Hui Zhao; Jianmin Sun (Molecular Biology Reports, 2024)

KLK7, KLK10, and KLK11 in Papillary Thyroid Cancer: Bioinformatic Analysis and Experimental Validation - Tao Ni; Ru-hua Zhao; Jing-fang Wu; Chao-you Li; Gang Xue; Xu Lin (Biochemical Genetics, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Physicochemical properties, structural characteristics and protein digestibility of pea protein-wheat gluten composited meat analogues prepared via high-moisture extrusion - Yu-Ru Zhao; Ning Peng; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Cai-Yue Wang; Zi-Yue Wang; Chenying Wang; Xidong Ren (Food Hydrocolloids, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Role of Nitrogen-doping in porous carbon for enlarging working voltage window of aqueous supercapacitors in neutral electrolyte - Shao-Wen Xu; Jing-Xuan Dai; Meng-Die Wang; Ru-Yue Zhu; Yong-Qing Zhao (Chemical Engineering Journal, 2024)

Associations between glycated haemoglobin and multi-modal imaging markers of early cardiac aging - Abigail C. C. Chng; Hong Chang Tan; Louis L. Y. Teo; Ru-San Tan; See Hooi Ewe; Shuang Leng; Xiao-Dan Zhao; Liang Zhong; Woon-Puay Koh; Jean-Paul Kovalik; Fei Gao; Angela S. Koh (GeroScience, 2024)

Fruit flexible collecting trajectory planning based on manual skill imitation for grape harvesting robot - Jiahui Sun; Qingchun Feng; Yifan Zhang; Mengfei Ru; Yajun Li; Tao Li; Chunjiang Zhao (Computers and Electronics in Agriculture, 2024)

Ubiquity and ecological risks of conjugated steroids cannot be overlooked: First evidence from estuarine sediments - Fei Tian; Shan Liu; Ru Xu; Nian-Nian Wu; Shuang-Shuang Liu; Yuan-Yue Cheng; Qian Xiong; Zhen-Zhao Tang; Lin-Bao Zhang; Zhe Zhang; Hai-Gang Chen (Marine Pollution Bulletin, 2024)

Assessing the role of urban green infrastructure in mitigating summertime Urban Heat Island (UHI) effect in metropolitan Shanghai, China - Hao Zhang; Meng-yuan Kang; Zhen-ru Guan; Rui Zhou; Ai-lian Zhao; Wen-jia Wu; Hao-rong Yang (Sustainable Cities and Society, 2024)

Neurotoxicity of fine and ultrafine particulate matter: A comprehensive review using a toxicity pathway-oriented adverse outcome pathway framework - Shuang-Jian Qin; Qing-Guo Zeng; Hui-Xian Zeng; Shen-Pan Li; John Andersson; Bin Zhao; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Nan-Xiang Jin; Mo Yang; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Interactions with soy lecithin regulate the emulsification capacity of pea protein: Effects of soy lecithin concentration - Boxue Xia; Yi Shen; Ru Zhao; Jie Deng; Cuina Wang (Food Hydrocolloids, 2024)

Lowering Schottky barrier in MoC-based cocatalyst via heteroatoms tunning for enhanced photocatalytic hydrogen evolution - Ru-zhou Miao; Yu-long Bao; Guang Yang; Ying-jie Sun; Xiao-jing Wang; Jun Zhao; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2024)

Chemical constituents from Ficus tikoua and chemotaxonomic significance - Han-Lei Wang; Jing Lu; Xue-Lin Chen; Ru Li; Kun Zhang; Yu-Ling Guo; Xia Zhao; Yu-Mei Zhang (Biochemical Systematics and Ecology, 2024)

Identification and fine mapping of a QTL-rich region for yield- and quality-related traits on chromosome 4BS in common wheat (Triticum aestivum L.) - Jinghui Li; Huanhuan Zhao; Minghu Zhang; Chan Bi; Xiaoyuan Yang; Xintian Shi; Chaojie Xie; Baoyun Li; Guangbin Ma; Zhengang Ru; Tiezhu Hu; Mingshan You (Theoretical and Applied Genetics, 2024)

Magnetic conjugated microporous polymer for rapid extraction and sensitive analysis of environmental endocrine disruptors in environmental waters and dairy products - Hai-Long Jiang; Fu-Shuai Kang; Ye-Fei Fan; Xia Wang; Yun-Liang Lin; Lu Liu; Wei Liu; Yan-Fang Zhao; Ru-Song Zhao (Analytica Chimica Acta, 2024)

Unraveling the characteristics of microplastics in agricultural soils upon long-term organic fertilizer application: A comprehensive study using diversity indices - Sen Guo; Guangmin Xiao; Yanhua Chen; Jiajia Zhang; Baogui Zhang; Shuhua Ru; Meng Zhao (Chemosphere, 2024)

Applications in Pickering emulsions of enhancing preservation properties: Current trends and future prospects in active food packaging coatings and films - Yiyi Cheng; Xuemei Cai; Xin Zhang; Yadong Zhao; Ru Song; Yan Xu; Haiyan Gao (Trends in Food Science & Technology, 2024)

Land surface response to groundwater drawdown and recovery in Taiyuan city, Northern China, analyzed with a long-term elevation change measurements from leveling and multi-sensor InSAR - Wei Tang; Xiangjun Zhao; Jinyang Wang; Mahdi Motagh; Huipeng Xu; Zhemin Ru; Yiming Wang (Journal of Hydrology, 2024)

Refining metallic nano-copper by electron-rich black carbon for superior Fenton-like catalysis in water purification: The capacitive regulation of corrosive electron transfer - Lu Zhao; Xing-Bo Chen; Xin-Ru Hu; Lei Chen; Shun Feng; Ai-Yong Zhang; Shu-Chuan Peng; Zhi-Xian Lin; Chu Jiang; Wei Da; Qi-Xin Wei (Journal of Hazardous Materials, 2024)

Pollution level and ecological risk assessment of triazine herbicides in Laizhou Bay and derivation of seawater quality criteria - Zhenzhong Zhang; Yongliang Feng; Weizhong Wang; Shaoguo Ru; Lingchao Zhao; Yuanqing Ma; Xiukai Song; Lijuan Liu; Jun Wang (Journal of Hazardous Materials, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Targeted liposomes for macrophages-mediated pulmonary fibrosis therapy - Yujie Wang; Fang Zhao; Xiangyu Wang; Haojie Zuo; Yiming Ru; Xi Cao; Yang Wang (Drug Delivery and Translational Research, 2024)

Determination of operation parameters for magnesium-air fuel cell to recover nitrogen and phosphorus from wastewater - Xingze Li; Sizhuo Wan; Tingting Dong; Zhiguo Zhao; Ru Wang (Journal of Environmental Management, 2024)

Digestion and absorption characteristics of iron-chelating silver carp scale collagen peptide and insights into their chelation mechanism - Qiannan Zhao; Wei Liang; Zhe Xiong; Chuan Li; Lu Zhang; Jianhua Rong; Shanbai Xiong; Ru Liu; Juan You; Tao Yin; Yang Hu (Food Research International, 2024)

Effect of guar gum, gelatin, and pectin on moisture changes in freeze-dried restructured strawberry blocks - Jiaqi Hu; Xiyun Sun; Hongwei Xiao; Chunju Liu; Feifei Yang; Wuyi Liu; Yulong Wu; Yaoyao Wang; Ru Zhao; Haiou Wang (Food Chemistry, 2024)

LECT2 mediates antibacterial immune response induced by Nocardia seriolae infection in the northern snakehead - Jian Teng; Yan Zhao; Yu Bao Li; Liang Yi Xue; Yi Xiang Zhai; Jian Ru Liu; Hui Wang; Xiang Shan Ji (Fish & Shellfish Immunology, 2024)

Novel pyrrolidine-alkylamino-substituted dicyanoisophorone derivatives as near-infrared fluorescence probe for imaging β-amyloid in vitro and in vivo - Hui Zhou; Jihang Zhai; Huiyuan Gong; Ru Fang; Yongmei Zhao; Wen Luo (Analytica Chimica Acta, 2024)

Distance-decay equations of antibiotic resistance genes across freshwater reservoirs - Zhao-Feng Guo; Kiranmoy Das; Wiebke J. Boeing; Yao-Yang Xu; Edoardo Borgomeo; Dong Zhang; Si-Cheng Ao; Xiao-Ru Yang (Water Research, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Nano‑selenium alleviates cadmium-induced blood-brain barrier destruction by restoring the Wnt7A/β-catenin pathway - Chen-Xi Li; Milton Talukder; Zhao-Yi Wang; Shi-Yong Zhu; Ya-Ru Xu; Xue-Nan Li; Jin-Long Li (Science of The Total Environment, 2024)

Hydroxyl-containing triazine-based conjugated microporous polymers for solid phase extraction of fluoroquinolone antibiotics in the environment and food samples - Lu-Shu Meng; Xiao-Li Wang; Xia Wang; Lei Ji; Lei-Lei Wang; Ya-Qi Cai; Ru-Song Zhao (Food Chemistry, 2024)

Adsorption Kinetics and Stabilization Effects of Various Forms of Phosphorus on Schwertmannite - Shuqin Bai; Ru Ya; Shuxuan Chen; Niqi Ao; Yiwen Wu; Qiyao Sun; Han Yang; Shuangfeng Zhao (Water, Air, & Soil Pollution, 2024)

Genome-wide identification of the SAUR gene family and screening for SmSAURs involved in root development in Salvia miltiorrhiza - Wei Wang; Yuwei Zheng; Lin Qiu; Dongfeng Yang; Ziyang Zhao; Yuanyuan Gao; Ru Meng; Hongguang Zhao; Shuncang Zhang (Plant Cell Reports, 2024)

Efficient activation of peracetic acid by cobalt modified nitrogen-doped carbon nanotubes for drugs degradation: Performance and mechanism insight - Mingya Yao; Shuofeng Zhang; Meng Xie; Lingxi Zhao; Ru-Song Zhao (Chemosphere, 2024)

Visible-light-driven photocatalytic degradation of ibuprofen by Cu-doped tubular C3N4: Mechanisms, degradation pathway and DFT calculation - Zhi-Bang Lv; Jiao Feng; Ru-Jin Zhao; Jun-Jian Shen; Wen-Wen Yang (Chemosphere, 2024)

Sex-inclined microRNAs in serum exosomes for sex determination in the greater amberjack (Seriola dumerili) - Qiuxia Deng; Yang Huang; Can Zhao; Xiaoying Ru; Ruijuan Hao; Na Zhao; Bo Zhang; Chunhua Zhu (Aquaculture, 2024)

Cysteine and glycine-rich protein 2 is crucial for maintaining the malignant phenotypes of gliomas through its action on Notch signalling cascade - Lingtong Liu; Fei Li; Lingxue Zhang; Yingying Cheng; Lin Wu; Ru Tie; Xiaobing Jiang; Wenwen Gao; Bochuan Liu; Yao Wei; Pan Chang; Jun Xu; et al. (Toxicology and Applied Pharmacology, 2024)

Glutamate application maintains quality and antioxidant capacity of fresh-cut carrots by modulating GABA shunt, phenylpropanoid and ROS metabolism - Jinglin Zhang; Jing Zhao; Xiaoxia Zuo; Wanli You; Xueyin Ru; Feng Xu; Peng Jin; Yonghua Zheng; Shifeng Cao (Food Chemistry, 2024)

Sex-specific impacts of thimerosal on the behaviors and brain monoaminergic systems in zebrafish (Danio rerio) - Xuchun Qiu; Zhen Su; Jiarui Gao; Yiming Cui; Kejun Dong; Kun Chen; Ru-Jin Zhao; Songmei Wang; Tao Wu; Yanhong Shi (Aquatic Toxicology, 2024)

Di- and tri-methylation of histone H3K36 play distinct roles in DNA double-strand break repair - Runfa Chen; Meng-Jie Zhao; Yu-Min Li; Ao-Hui Liu; Ru-Xin Wang; Yu-Chao Mei; Xuefeng Chen; Hai-Ning Du (Science China Life Sciences, 2024)

Initiation and Propagation of Interface Cracks in Layered Composite Rocks: An Investigation Using True Triaxial Experiments - Jian-Zhi Zhang; Tian-Tian Gu; Ru-Fang Zhan; Zhao-Peng Zhang (Geotechnical and Geological Engineering, 2024)

BDNF mimetics recover palmitic acid-induced injury in cardiomyocytes by ameliorating Akt-dependent mitochondrial impairments - Man-Ru Zhang; Bang-Yun Zuo; Yu-Chen Song; Dan-Dan Guo; Qing-Liu Li; Jin-Xiu Lyu; Hua Zhu; Jing Zhao; Peng-Zhou Hang (Toxicology and Applied Pharmacology, 2024)

Green manure removal with reduced nitrogen improves saline-alkali soil organic carbon storage in a wheat-green manure cropping system - Fangdi Chang; Hongyuan Zhang; Na Zhao; Peiyi Zhao; Jiashen Song; Ru Yu; Zhengrong Kan; Xiquan Wang; Jing Wang; Hanjiang Liu; Dongxun Han; Xinya Wen; et al. (Science of The Total Environment, 2024)

The specialized sesquiterpenoids produced by the genus Elephantopus L.: Chemistry, biological activities and structure-activity relationship exploration - Qian-Ru Rao; Jian-Bo Rao; Min Zhao (Phytochemistry, 2024)

Comprehensive impacts of the presence of proton exchange membrane on the efficiency of Mg-air fuel cell to remove nutrients and recover struvite - Tingting Dong; Xingze Li; Zhiguo Zhao; Ru Wang (Journal of Water Process Engineering, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Downhole detection of gas kick using low-frequency elastic wave: Multiphysics modeling and its implications - Zizhen Wang; Ru Zhao; Yanbin Zang; Weidong Zhou; Guanlin Chen; Rui Zhang (Gas Science and Engineering, 2024)

High-Performance enrichment and sensitive analysis of bisphenol and its analogues in water and milk using a novel Ni-Based cationic Metal-Organic framework - Jin-Yan Ma; Hai-Long Jiang; Fu-Shuai Kang; Lu Liu; Xia Wang; Ru-Song Zhao (Food Chemistry, 2024)

Development, characteristics and biological activities of bilayer composite film based on gelatin/κ-carrageenan loading curcumin and ε-polylysine - Xihan Yang; Minzhen Zhang; Baoding Zhao; Xiaoyu Zou; Ru Song (Food Hydrocolloids, 2024)

Efficient removal of size-fractionated antibiotic resistance genes (ARGs) in WWTPs secondary effluent by vacuum ultraviolet (VUV) activated potassium peroxymonosulfate (PMS) - Xiao-Yan Fan; Shi-Long Xu; Xing Li; Zhi-Wei Zhou; Yu-Xi Gao; Jun-Ru Zhao; Zhong-Xing Zhang (Chemical Engineering Journal, 2024)

Microbial antagonistic mechanisms of Hg(II) and Se(IV) in efficient wastewater treatment using granular sludge - Zhanfei He; Jiaquan Shen; Yuanhai Zhao; Yulong Ru; Daoyong Zhang; Xiangliang Pan (Water Research, 2024)

Opportunist ant species dominate metropolitan microhabitats: Evidence from the eastern margin of the Qinghai-Tibetan plateau - Ru-Yi Yin; Xin-Yu Luo; Xiang-Qin Huang; Zi-Xuan Zhao; Chris Newman; Yi Luo; Zhao-Min Zhou (Soil Biology and Biochemistry, 2024)

Proteomics revealed composition- and size-related regulators for hepatic impairments induced by silica nanoparticles - Xinying Zhao; Ru Ma; Alimire Abulikemu; Yi Qi; Xiaoying Liu; Ji Wang; Kun Xu; Caixia Guo; Yanbo Li (Science of The Total Environment, 2024)

Fabrication of hyaluronic acid-altered gold complex delivery for head and neck squamous cell carcinoma therapy with high antitumor efficacy and low in vivo toxicity - Shizhi He; Jiaming Chen; Yanming Zhao; Ru Wang; Yurong He; Shaoshi Chen; Yifan Yang; Changyu Zhu; Jingyang Zhao; Jugao Fang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Risk factors for short-term prognosis of end-stage liver disease complicated by invasive pulmonary aspergillosis - Weiyan Yu; Ying Xiao; Yue Luo; Yangyang Hu; Ru Ji; Wei Wang; Zhinian Wu; Zeqiang Qi; Tingyu Guo; Yadong Wang; Caiyan Zhao (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Ecological risk assessment of heavy metals in desulfurized seawater discharged from a coal-fired power plant in Qingdao - Yongliang Feng; Yiran Ru; Jun Wang; Xiaona Zhang; Hua Tian; Shuhe Lei; Ziang Zhao; Shaoguo Ru (Ecotoxicology, 2024)

Longitudinal aortic strain, ventriculo-arterial coupling and fatty acid oxidation: novel insights into human cardiovascular aging - Hongzhou Zhang; Shuang Leng; Fei Gao; Jean-Paul Kovalik; Ru-San Tan; Hai Ning Wee; Kee Voon Chua; Jianhong Ching; Xiaodan Zhao; John Allen; Qinghua Wu; Tim Leiner; et al. (GeroScience, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Study by means of 1H nuclear magnetic resonance of the oxidation process in high oleic sunflower oil and palm oil during deep-frying of fish cakes - Xiaoyu Luo; Benlun Hu; Caihua Jia; Ru Liu; Jianhua Rong; Siming Zhao; Meng Niu; Yan Xu; Tao Yin; Juan You (Food Research International, 2024)

Preparation and characterization of pea protein isolate-egg white protein composite gels - Yu-Ru Zhao; Ning Peng; Chenying Wang; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Ao-Yue Sun; Xidong Ren (Food Hydrocolloids, 2024)

Tea polyphenols alleviate TBBPA-induced inflammation, ferroptosis and apoptosis via TLR4/NF-κB pathway in carp gills - Ran Xu; Fu-xin Han; Hong-ru Wang; Jing-jing Wang; Zhao-long Cai; Meng-yao Guo (Fish & Shellfish Immunology, 2024)

Efficient and synergistic treatment of selenium (IV)-contaminated wastewater and mercury (II)-contaminated soil by anaerobic granular sludge: Performance and mechanisms - Zhanfei He; Jiaquan Shen; Yuanhai Zhao; Yulong Ru; Daoyong Zhang; Xiangliang Pan (Chemosphere, 2024)

Adaptive shifts in plant traits associated with nitrogen removal driven by phytoremediation strategies in subtropical river restoration - Yu Xin; Lin Liu; Xiao-Ru Yang; Le-Yang Yang; Shan-Bin Guang; Yu-Ming Zheng; Quan-Bao Zhao (Water Research, 2024)

Advances in the study of silica nanoparticles in lung diseases - Li-Hong Ao; Yun-Geng Wei; Hong-Ru Tian; Hua Zhao; Jun Li; Jia-Qi Ban (Science of The Total Environment, 2024)

Efficient electro-demulsification of O/W emulsions and simultaneous oil removal enabled by a multiscale porous biocarbon electrode - Kui Wang; Hailiang Zhao; Yingming Zhang; Xu Li; Mengyi Xu; Meirong Song; Guangxin Ru; Xiaolei Jiang; Xiuhong Zhu; Dandan Han; Yutao Dong; Kexin Shen; et al. (Chemical Engineering Journal, 2024)

Mixed sowing of Feed rape and Vicia villosa can substitute nitrogen fertilizer to improve soil multifunctionality in the Hetao irrigation District - Ru Yu; Hongyuan Zhang; Fangdi Chang; Jiashen Song; Jing Wang; Xiquan Wang; Zhengrong Kan; Na Zhao; Xiaohong Li; Jun Ma; Yuyi Li (CATENA, 2024)

Mechanism of enhanced microalgal biomass and lipid accumulation through symbiosis between a highly succinic acid-producing strain of Escherichia coli SUC and Aurantiochytrium sp. SW1 - Mei-Yu Zhang; Xin-Ru Xu; Ru-Ping Zhao; Chao Huang; Yuan-Da Song; Zi-Tong Zhao; Yu-Bin Zhao; Xiao-Jie Ren; Xin-He Zhao (Bioresource Technology, 2024)

Rapid detection of human adenovirus subgroup B using recombinase polymerase amplification assay - Yongzhe Zhu; Binghui Xia; Haizhou Xu; Zengxin Liu; Ru Wang; Qingqing Cai; Ping Zhao; Zhongtian Qi (Virus Genes, 2024)

Peduncle collision-free grasping based on deep reinforcement learning for tomato harvesting robot - Yajun Li; Qingchun Feng; Yifan Zhang; Chuanlang Peng; Yuhang Ma; Cheng Liu; Mengfei Ru; Jiahui Sun; Chunjiang Zhao (Computers and Electronics in Agriculture, 2024)

Is there a relationship between economic growth and natural resource commodity price volatility? Evidence from China - Ru Zhang; Wenhao Zhao; Yong Wang (Resources Policy, 2024)

Accelerated removal of naproxen in the iron-based peracetic acid activation system by chloride ions: Enhancement of reactive oxidative species via the formation of iron-chloride complexes - Si-Ying Yu; Yang Shi; Chuan-Shu He; Yu-Dan Dong; Si Sun; Ru-Yan Ning; Zhao-Kun Xiong; Peng Zhou; Heng Zhang; Bo Lai (Journal of Hazardous Materials, 2024)

Tree ring oxygen isotope in Asia - Chenxi Xu; Ru Huang; Wenling An; Qingyu Zhao; Yaru Zhao; Junbo Ren; Yucheng Liu; Zhengtang Guo (Global and Planetary Change, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

Nitrite acts as the key “switch” governing the free nitrous acid pretreatment in anaerobic digestion: A comprehensive mechanism of abiotic, bioinformatics and bioenergetics effects - Zhibang Han; Ru Fang; Xueting Wang; Guangchen Huang; Dong Wu; Jun Tai; Bing Xie; Yinglong Su; Jingyang Luo; Gang Zhao; Ming Jiang (Chemical Engineering Journal, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Effect of swimming training on the flesh quality in Chinese Perch (Siniperca chuatsi) and its relationship with muscle metabolism - Tingyao Zhu; Ru Yang; Runguo Xiao; Weiqiang Ni; Liwei Liu; Jian Zhao; Zhangying Ye (Aquaculture, 2023)

Plastic pollution from takeaway food industry in China - Qian-Qian Zhang; Min-Yi Lan; Hui-Ru Li; Shu-Qing Qiu; Zhao Guo; You-Sheng Liu; Jian-Liang Zhao; Guang-Guo Ying (Science of The Total Environment, 2023)

Genome resources for the elite bread wheat cultivar Aikang 58 and mining of elite homeologous haplotypes for accelerating wheat improvement - Jizeng Jia; Guangyao Zhao; Danping Li; Kai Wang; Chuizheng Kong; Pingchuan Deng; Xueqing Yan; Xueyong Zhang; Zefu Lu; Shujuan Xu; Yuannian Jiao; Kang Chong; et al. (Molecular Plant, 2023)

Polyethylene microplastics cause apoptosis via the MiR-132/CAPN axis and inflammation in carp ovarian - Meng-ran Zhu; Hong-ru Wang; Fu-xin Han; Zhao-long Cai; Jing-jing Wang; Meng-yao Guo (Aquatic Toxicology, 2023)

Antioxidant CeO2 doped with carbon dots enhance ammonia production by an electroactive Azospirillum humicireducens SgZ-5T - Gao-Kai Wu; Meng-Xin Zhao; Si-Ru Chen; Yi-Nan Sun; Su-Fang Qin; Ai-Jun Wang; Qun-Feng Ye; Hend Alwathnani; Le-Xing You; Christopher Rensing (Chemosphere, 2023)

Mechanical energy-driven triboelectric plasma catalytic CO2 reduction over oxygen-vacancy-introduced In2O3 nanoparticles - Xiaochen Xiang; Jiao Wang; Qinglong Ru; Sumin Li; Ke Zhao; Yifei Zhu; Zhenpan Chen; Liangliang Liu; Guangqin Gu; Yu Jia; Bao Zhang; Gang Cheng; et al. (Chemical Engineering Journal, 2023)

Cyclodextrin-based metal-organic framework materials: Classifications, synthesis strategies and applications in variegated delivery systems - Ru-nan Zhao; Bei-wei Zhu; Yu Xu; Song-feng Yu; Wen-jun Wang; Dong-hong Liu; Jiang-ning Hu (Carbohydrate Polymers, 2023)

Intermittent fasting and Alzheimer's disease—Targeting ketone bodies as a potential strategy for brain energy rescue - Yu- Cai Ye; Shi-Fan Chai; Xin-Ru Li; Mei-Na Wu; Hong-Yan Cai; Zhao-Jun Wang (Metabolic Brain Disease, 2023)

Boron nitride quantum dots-enhanced laser desorption/ionization mass spectrometry analysis and imaging of bisphenol A - Yanfang Zhao; Rabah Boukherroub; Lu Liu; Huizhi Li; Ru-Song Zhao; Qin Wei; Xiang Yu; Xiangfeng Chen (Journal of Hazardous Materials, 2023)

Adsorption behaviors and bioavailability of tetrabromobisphenol A in the presence of polystyrene microplastic in soil: Effect of microplastics aging - Jianning Chang; Jinsong Liang; Wei Fang; Haibo Zhang; Yajie Zhang; Hongjun Zhao; Ru Zhang; Panyue Zhang; Guangming Zhang (Environmental Pollution, 2023)

Fungal strain improvement for efficient cellulase production and lignocellulosic biorefinery: Current status and future prospects - Jie Yang; Hou-Ru Yue; Li-Ya Pan; Jia-Xun Feng; Shuai Zhao; Surisa Suwannarangsee; Verawat Champreda; Chen-Guang Liu; Xin-Qing Zhao (Bioresource Technology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Metabolomic profiling of Panax ginseng in response to Fusarium solani infection - Guijia Zhao; Shuyang Xing; Yang Wang; Xu Yang; Ru Sun; Lin Feng; Jifeng Wang; Tianxia Sun; Wenhui Lian; Yu Zhao (Physiological and Molecular Plant Pathology, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

Effects of combined antibiotics on nitrification, bacteria and antibiotic resistance genes in activated sludge: Insights from legacy effect of antibiotics - Zhong-Xing Zhang; Xiao-Yan Fan; Xing Li; Yu-Xi Gao; Jun-Ru Zhao (Journal of Environmental Sciences, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Enhancing fiber–matrix interface permeability resistance of natural fiber-reinforced, bio-cemented sand by CaCO 3 seed pretreatment - Liang Guo; Qichen Dai; Xingzhu Lin; Yuhong Jiang; Baoquan Wang; Xiaohua Pan; Yiqi Peng; Guoqiang Zhao; Yi Ru; Liye Zhou (Geomechanics for Energy and the Environment, 2023)

The effect of gene flow on frost tolerance in Scots pine – Latitudinal translocation of genetic material - David Hall; Wei Zhao; Alisa Heuchel; Jie Gao; Ulfstand Wennström; Xiao-Ru Wang (Forest Ecology and Management, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

(±)-Sarcanan A, a pair of new enantiomeric dihydrobenzofuran neolignans from the aerial parts of Sarcandra glabra - Ju Liu; Qi-yin Wen; Hong-ru Tian; Bing-jin-feng Zhan; Long-ping Zhu; De-po Yang; Zhi-min Zhao (Natural Product Research, 2023)

A hybrid optimized model for predicting evapotranspiration in early and late rice based on a categorical regression tree combination of key influencing factors - Long Zhao; Shunhao Qing; Jiayi Bai; Haohao Hao; Hui Li; Yi Shi; Xuguang Xing; Ru Yang (Computers and Electronics in Agriculture, 2023)

Effect of slaughter age and postmortem aging time on tenderness and water-holding capacity of yak (Bos grunniens) longissimus thoracis muscle - Xueyuan Bai; Feng Yin; Ang Ru; Wei Tian; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Jiahui Li; Mancai Yin; Chaozhi Zhu; Gaiming Zhao (Meat Science, 2023)

The sustainable treatment of chemical polishing wastewater under low-carbon economy: Pollutants removal, resource recovery and energy generation - Cong Ding; Meng-yu Liu; Si-zhuo Wan; Zhao-yang Cai; Lin-jiang Yuan; Ru Wang; Ping Zheng (Journal of Cleaner Production, 2023)

Au@BN-enhanced laser desorption/ionization mass spectrometry and imaging for determination of fipronil and its metabolites in food and biological samples - Yanfang Zhao; Rabah Boukherroub; Guiju Xu; Huijuan Li; Ru-Song Zhao; Qin Wei; Xiang Yu; Xiangfeng Chen (Food Chemistry, 2023)

Lycopene-loaded emulsions stabilized by whey protein covalently modified with pectin or/and chlorogenic acid: Enhanced physicochemical stability and reduced bio-accessibility - Yuanyuan Zhang; Tiehua Zhang; Chao Dong; Ru Zhao; Xiaoge Zhang; Cuina Wang (Food Chemistry, 2023)

Effect of liver metastasis on the efficacy of immune checkpoint inhibitors in cancer patients: a systemic review and meta-analysis - Bao-Wen Tian; Cheng-Long Han; Han-Chao Wang; Lun-Jie Yan; Zi-Niu Ding; Hui Liu; Xin-Cheng Mao; Jin-Cheng Tian; Jun-Shuai Xue; Long-Shan Yang; Si-Yu Tan; Zhao-Ru Dong; et al. (Clinical & Experimental Metastasis, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Xanthine-derived reactive oxygen species exacerbates adipose tissue disorders in male db/db mice induced by real-ambient PM2.5 exposure - Leijian Chen; Huankai Li; Yi Ru; Yuanyuan Song; Yuting Shen; Lifang Zhao; Gefei Huang; Yi Chen; Zenghua Qi; Ruijin Li; Chuan Dong; Jiacheng Fang; et al. (Science of The Total Environment, 2023)

Silica nanoparticles promoted pro-inflammatory macrophage and foam cell transformation via ROS/PPARγ/NF-κB signaling - Caixia Guo; Xinying Zhao; Ru Ma; Lingnan Zhu; Yueyue Chen; Zhu Yang; Zongwei Cai; Zhiwei Sun; Yanbo Li (Science of The Total Environment, 2023)

Gestational 1-nitropyrene exposure causes anxiety-like behavior partially by altering hippocampal epigenetic reprogramming of synaptic plasticity in male adult offspring - Bo Wang; Ting Zhao; Xiao-Xi Chen; Yan-Yan Zhu; Xue Lu; Qing-Hua Qian; Hui-Ru Chen; Xiu-Hong Meng; Hua Wang; Wei Wei; De-Xiang Xu (Journal of Hazardous Materials, 2023)

Effects of flow velocity on the growth performance, antioxidant activity, immunity and intestinal health of Chinese Perch (Siniperca chuatsi) in recirculating aquaculture systems - Tingyao Zhu; Ru Yang; Runguo Xiao; Liwei Liu; Songming Zhu; Jian Zhao; Zhangying Ye (Fish & Shellfish Immunology, 2023)

Highly sensitive plasmonic biosensor for hepatitis B virus DNA based on the surface etching of the active helical gold nanorods - Ru Cheng; Liang Tong Li; Min Huang; Fu Zhu; Qian Li; Hui Liu; Jie Gao; Xiao Hui Zhao; Fu Kang Luo; Jian Wang (Chemical Engineering Journal, 2023)

Factors influencing the spatial distribution and individual variation in urinary fluoride levels in Tibet, China - Ru Zhang; Yi Yang; Yangzong Deji; Hairong Li; Yonghua Li; Cangjue Nima; Shengcheng Zhao; Hongqiang Gong (Chemosphere, 2023)

Soil erosion effectively alleviated by Miscanthus sacchariflorus, a potential candidate for land deterioration improvement - Chu Zhao; Yu-han Nie; Jian-pan Xin; Xiao-yu Zhu; Yan Li; Ru-nan Tian (Rhizosphere, 2023)

Chemical diversity and biological activities of specialized metabolites from the genus Chaetomium: 2013–2022 - Qian-Ru Rao; Jian-Bo Rao; Min Zhao (Phytochemistry, 2023)

Study on of structural style of fault zone and reservoir characteristics in the northern slope of Tazhong Uplift, Tarim Basin, China - Rui Zhao; Yuan Kang; Jun Han; Xiuxiang Zhu; Teng Zhao; Yuqing Liu; Chongyang Xiao; Shang Deng; Zhixing Ru; Yingtao Li (Carbonates and Evaporites, 2023)

An extended SW-TES algorithm for land surface temperature and emissivity retrieval from ECOSTRESS thermal infrared data over urban areas - Chen Ru; Si-Bo Duan; Xiao-Guang Jiang; Zhao-Liang Li; Cheng Huang; Meng Liu (Remote Sensing of Environment, 2023)

Bergamotane-type sesquiterpenes from the leaves and twigs of Illicium oligandrum and their anti-inflammatory activities - Wen-Rui Li; Jia-Ying Zhao; Mi Li; Xiao-Jing Wang; Guo-Zhu Su; Hai-Qiang Wang; Li Li; Guan-Hua Du; Ru-Bing Wang; Shuang-Gang Ma (Phytochemistry, 2023)

Cadmium aggravates the blood-brain barrier disruption via inhibition of the Wnt7A/β-catenin signaling axis - Chen-Xi Li; Milton Talukder; Ya-Ru Xu; Shi-Yong Zhu; Ying-Xin Zhao; Jin-Long Li (Environmental Pollution, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

A volatile producing Bacillus subtilis strain from the rhizosphere of Haloxylon ammodendron promotes plant root development - Ao-Lei He; Ling-Yu Zhao; Wei Ren; Hui-Ru Li; Paul W. Paré; Qi Zhao; Jin-Lin Zhang (Plant and Soil, 2023)

A novel oxygen vacancies enriched Co Ni LDO catalyst activated peroxymonosulfate for the efficient degradation of tetracycline - Hao-Liang Jiang; Ming-Hui Li; Ling-Xi Zhao; Zhao-Xing Yan; Meng Xie; Jin-Ming Lin; Ru-Song Zhao (Journal of Water Process Engineering, 2023)

Magnetic ternary layered double hydroxides for efficient removal of 1-naphthalene acetic acid from waters: Adsorption behavior and mechanism - Ti-Bo Fang; Hua Xiao; Ling-Xi Zhao; Na Li; Ling-Yu Luan; Zhao-Xing Yan; Jin-Ming Lin; Ru-Song Zhao (Journal of Environmental Chemical Engineering, 2023)

Pharmacokinetic profile and sub-chronic toxicity of coenzyme Q10 loaded whey protein nanoparticles - Cuina Wang; Ru Zhao; Keyi He; Siyu Zhang; Alyssa H. Kemp; Mingruo Guo (Food Bioscience, 2023)

A Cre knockin mouse reveals specific expression of Agouti gene in mesenchymal lineage cells in multiple organs and provides a unique tool for conditional gene targeting - Xing-Ru Shen; He-Li Zhang; Xu-Bo Zhao; Yang-Ge Wang; Xiao-Yang Tan; Lipeng Gao; Ruilin Sun; Xin-Hua Liao (Transgenic Research, 2023)

Genomic vulnerability to climate change in Quercus acutissima , a dominant tree species in East Asian deciduous forests - Shuai Yuan; Yong Shi; Biao‐Feng Zhou; Yi‐Ye Liang; Xue‐Yan Chen; Qing‐Qing An; Yan‐Ru Fan; Zhao Shen; Pär K. Ingvarsson; Baosheng Wang (Molecular Ecology, 2023)
Understanding the evolutionary processes that shape the landscape of genetic variation and influence the response of species to future climate change is critical for biodiversity conservation. Here, we sampled 27 populations across the distribution range of a dominant forest tree, Quercus acutissima , in East Asia, and applied genome‐wide analyses to track the evolutionary history and predict the fate of populations under future climate. We found two genetic groups (East and West) in Q. acutissima that diverged during Pliocene. We also found a heterogeneous landscape of genomic variation in this species, which may have been shaped by population demography and linked selections. Using genotype‐environment association analyses, we identified climate‐associated SNPs in a diverse set of genes and functional categories, indicating a model of polygenic adaptation in Q. acutissima . We further estimated three genetic offset metrics to quantify genomic vulnerability of this species to climate change due to the complex interplay between local adaptation and migration. We found that marginal populations are under higher risk of local extinction because of future climate change, and may not be able to track suitable habitats to maintain the gene–environment relationships observed under the current climate. We also detected higher reverse genetic offsets in northern China, indicating that genetic variation currently present in the whole range of Q. acutissima may not adapt to future climate conditions in this area. Overall, this study illustrates how evolutionary processes have shaped the landscape of genomic variation, and provides a comprehensive genome‐wide view of climate maladaptation in Q. acutissima .

Characterization of microbial community, ecological functions and antibiotic resistance in estuarine plastisphere - Le-Yang Yang; Xin-Rong Huang; Roy Neilson; Shu-Yi-Dan Zhou; Zhao-Lei Li; Xiao-Ru Yang; Xiao-Xuan Su (Science of The Total Environment, 2023)

Plant identity shapes phyllosphere microbiome structure and abundance of genes involved in nutrient cycling - Jian Li; Ming-Kang Jin; Roy Neilson; Shi-Lin Hu; Yi-Jia Tang; Zhao Zhang; Fu-Yi Huang; Jing Zhang; Xiao-Ru Yang (Science of The Total Environment, 2023)

Room-temperature synthesis of nitrogen-rich conjugated microporous polymers for solid-phase extraction of trace synthetic musks - Ye-Fei Fan; Hai-Long Jiang; Xiang-Feng Chen; Na Li; Xiao-Li Wang; Jin-Ming Lin; Ru-Song Zhao (Food Chemistry, 2023)

Dynamic changes in cell wall-degrading enzymes and physio-biochemistry of ginseng in response to fusarium oxysporum infection - Lin Feng; Guijia Zhao; Ru Sun; Jifeng Wang; Tianxia Sun; Shuyang Xing; Wenhui Lian; Yu Zhao (European Journal of Plant Pathology, 2023)

Can technological finance cooperation pilot policy improve energy efficiency? Evidence from a quasi-experiment in China - Bin Zhao; Ru-Yu Xu (Environmental Science and Pollution Research, 2023)

Condition optimization of iron-air fuel cell to treat phosphate-containing wastewater regarding sustainable development - Ling-ling Lai; Chao Liu; Meng-yu Liu; Si-zhuo Wan; Zhi-guo Zhao; Ru Wang; Lin-jiang Yuan (Chemosphere, 2023)

Response of activated sludge to antibiotics stress: Neglected legacy effects - Zhong-Xing Zhang; Xiao-Yan Fan; Xing Li; Yu-Xi Gao; Jun-Ru Zhao (Journal of Water Process Engineering, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

Restrictions on Niobium enrichment by alteration of Niobium-rich biotite in pure water, acid, alkaline and fluoride-bearing solutions at 200 MPa and 300–600 °C - Zhao-Yu Yang; Ru-Cheng Wang; Xu-Dong Che; Daniel Harlov (Geochimica et Cosmochimica Acta, 2023)

Treatment of heavy metal ions-polluted water into drinkable water: Capture and recovery of Pb2+ by cellulose@CaCO3 bio-composite filter via spatial confinement effect - He-Xiang Zhao; Yan Wang; Jun-Jie Yang; Ji-Guo Zhang; Yuan-Ru Guo; Shujun Li; Qing-Jiang Pan (Chemical Engineering Journal, 2023)

Formation Mechanism of Thick Coal Seam in the Lower Indus Basin, SE Pakistan - Hassan Nasir Mangi; Ru′an Chi; Jun Zhao; Detian Yan; Lara Sindhu; Dongsheng He; Zixin He; Jing Li; Umar Ashraf; Hongbo Wang (Natural Resources Research, 2023)

FTO inhibits oxidative stress by mediating m6A demethylation of Nrf2 to alleviate cerebral ischemia/reperfusion injury - Lijing Hou; Shuang Li; Shasha Li; Ru Wang; Mengke Zhao; Xiaomin Liu (Journal of Physiology and Biochemistry, 2023)

Analysis of Whole Blood and Urine Trace Elements in Children with Autism Spectrum Disorders and Autistic Behaviors - Gang Zhao; Si-jin Liu; Xin-yu Gan; Jun-ru Li; Xiao-xue Wu; Si-yan Liu; Yi-si Jin; Ke-rang Zhang; Hong-mei Wu (Biological Trace Element Research, 2023)
The relationship between trace elements and neurological development is an emerging research focus. We performed a case–control study to explore (1) the differences of 13 trace elements chromium (Cr), manganese (Mn), cobalt (Co), zinc (Zn), arsenic (As), selenium (Se), molybdenum (Mo), cadmium (Cd), stannum (Sn), stibium (Sb), mercury (Hg), titanium (TI), and plumbum (Pb) concentration in whole blood and urine between autism spectrum disorder (ASD) children and their typical development peers, and (2) the association between the 13 trace elements and core behaviors of ASD. Thirty ASD subjects (cases) and 30 age-sex-matched healthy subjects from Baise City, Guangxi Zhuang Autonomous Region, China, were recruited. Element analysis was carried out by inductively coupled plasma-optical emission spectrometry. Autistic behaviors were assessed using Autism Behavior Checklist (ABC), Childhood Autism Rating Scale (CARS), and Children Neuropsychological and Behavior Scale (CNBS). The whole blood concentrations of Mo ( p = 0.004), Cd (0.007), Sn ( p = 0.003), and Pb ( p = 0.037) were significantly higher in the ASD cases than in the controls. Moreover, Se (0.393), Hg (0.408), and Mn (− 0.373) concentrations were significantly correlated between whole blood and urine levels in ASD case subjects. There were significant correlations between whole blood Sb (0.406), Tl (0.365), Mo (− 0.4237), Mn (− 0.389), Zn (0.476), and Se (0.375) levels and core behaviors of ASD. Although the mechanism of trace element imbalance in ASD is unclear, these data demonstrate that core behaviors of ASD may be affected by certain trace elements. Further studies are recommended for exploring the mechanism of element imbalance and providing corresponding clinical treatment measures.

Contribution of Tibetan Plateau ecosystems to local and remote precipitation through moisture recycling - Yan Li; Ru Xu; Kun Yang; Yanxu Liu; Shuai Wang; Sha Zhou; Zhao Yang; Xiaoming Feng; Chunyang He; Zhengjie Xu; Wenwu Zhao (Global Change Biology, 2023)
The ecosystems of the Tibetan Plateau (TP) provide multiple important ecosystem services that benefit both local populations and those beyond, such as through climate regulation services on precipitation for East Asia and China. However, the precipitation regulation service of the TP ecosystems for supplying moisture and maintaining precipitation is yet to be evaluated. In this study, we used the moisture recycling framework and a moisture tracking model to quantify the precipitation regulation services of TP ecosystems for their contribution to precipitation. We found TP ecosystems contributed substantially to local and downwind precipitation, with a contribution of 221 mm/year for the TP and neighboring areas through evapotranspiration (ET) (104 mm/year through transpiration), declined to

Fiscal decentralization, industrial structure upgrading, and carbon emissions: evidence from China - Bin Zhao; Ke-Liang Wang; Ru-Yu Xu (Environmental Science and Pollution Research, 2023)

Proteomic profiling reveals dysregulated mitochondrial complex subunits responsible for myocardial toxicity induced by SiNPs - Xinying Zhao; Hailin Xu; Yan Li; Ru Ma; Yi Qi; Min Zhang; Caixia Guo; Zhiwei Sun; Yanbo Li (Science of The Total Environment, 2023)

Metallurgical performance and structural characteristics of cokes of hypercoal prepared from the mixture of low-rank coal and biomass residue - Jun Zhao; Hong Liu; Haochen Zhang; Xiaolin Song; Haibin Zuo; Guangwei Wang; Zhigao Xu; Ming Wu; Zhenyue Zhang; Ru'an Chi (Fuel, 2023)

The feasibility of skin mucus replacing exosome as a pool for bacteria-infected markers development via comparative proteomic screening in teleost - Na Zhao; Lei Jia; Qiumei Wang; Qiuxia Deng; Xiaoying Ru; Chunhua Zhu; Bo Zhang (Fish & Shellfish Immunology, 2023)

Identifying the impact of Fe nanoparticles encapsulated by nitrogen-doped carbon to Fe single atom sites for boosting oxygen reduction reaction toward Zn-air batteries - Wen-Jun Niu; Ying-Yun Yan; Ru-Ji Li; Wei-Wei Zhao; Jiang-Lei Chen; Ming-Jin Liu; Bingni Gu; Wen-Wu Liu; Yu-Lun Chueh (Chemical Engineering Journal, 2023)

Three-dimensional hydroxylated covalent organic frameworks for solid phase extraction of glucocorticoids in environmental water samples - Chuqing Liu; Guiju Xu; Baoyu Li; Xiaoli Wang; Jin-Ming Lin; Ru-Song Zhao (Analytica Chimica Acta, 2023)

Additional ratios of hydrolysates from lignocellulosic digestate at different hydrothermal temperatures influencing anaerobic digestion performance - Jing Wang; Nannan Zhao; Xuan Zhang; Lei Jiang; Ya-Ru Kang; Yi-Xuan Chu; Ruo He (Environmental Science and Pollution Research, 2022)

Lipocalin-2-Mediated Insufficient Oligodendrocyte Progenitor Cell Remyelination for White Matter Injury After Subarachnoid Hemorrhage via SCL22A17 Receptor/Early Growth Response Protein 1 Signaling - Qiang Li; Xufang Ru; Yang Yang; Hengli Zhao; Jie Qu; Weixiang Chen; Pengyu Pan; Huaizhen Ruan; Chaojun Li; Yujie Chen; Hua Feng (Neuroscience Bulletin, 2022)
Insufficient remyelination due to impaired oligodendrocyte precursor cell (OPC) differentiation and maturation is strongly associated with irreversible white matter injury (WMI) and neurological deficits. We analyzed whole transcriptome expression to elucidate the potential role and underlying mechanism of action of lipocalin-2 (LCN2) in OPC differentiation and WMI and identified the receptor SCL22A17 and downstream transcription factor early growth response protein 1 (EGR1) as the key signals contributing to LCN2-mediated insufficient OPC remyelination. In LCN-knockdown and OPC EGR1 conditional-knockout mice, we discovered enhanced OPC differentiation in developing and injured white matter (WM); consistent with this, the specific inactivation of LCN2/SCl22A17/EGR1 signaling promoted remyelination and neurological recovery in both atypical, acute WMI due to subarachnoid hemorrhage and typical, chronic WMI due to multiple sclerosis. This potentially represents a novel strategy to enhance differentiation and remyelination in patients with white matter injury.

Identification and bioinformatic analysis of the CaCesA/Csls family members and the expression of the CaCslD1 in the flower buds of CMS/Rf system in pepper - Panpan Duan; Min Wei; Ru Zhang; Shufang Zhao; Yongfu Wang; Bingdiao Gou; Nan Yang; Tao Zhang; Gaoyuan Zhang; Bingqiang Wei (Functional & Integrative Genomics, 2022)

Acute Toxicity of a Novel anti-fouling Material Additive DCOIT to Marine Chlorella sp - Jin-Chuang Ru; Xue-Li Zhao; Zhi-Han Cao; Cheng-Zhuang Chen; Ping Li; Zhi-Hua Li (Bulletin of Environmental Contamination and Toxicology, 2022)

PITPNC1 promotes the thermogenesis of brown adipose tissue under acute cold exposure - Guoqing Tang; Chengxin Ma; Liangkui Li; Shaoyan Zhang; Fengsheng Li; Jin Wu; Yesheng Yin; Qing Zhu; Yan Liang; Ru Wang; He Huang; Tong-Jin Zhao; et al. (Science China Life Sciences, 2022)
Brown adipose tissue (BAT) plays an essential role in non-shivering thermogenesis. The phosphatidylinositol transfer protein, cytoplasmic 1 (PITPNC1) is identified as a lipid transporter that reciprocally transfers phospholipids between intracellular membrane structures. However, the physiological significance of PITPNC1 and its regulatory mechanism remain unclear. Here, we demonstrate that PITPNC1 is a key player in thermogenesis of BAT. While Pitpnc1 −/− mice do not differ with wildtype mice in body weight and insulin sensitivity on either chow or high-fat diet, they develop hypothermia when subjected to acute cold exposure at 4°C. The Pitpnc1 −/− brown adipocytes exhibit defective β-oxidation and abnormal thermogenesis-related metabolism pathways in mitochondria. The deficiency of lipid mobilization in Pitpnc1 −/− brown adipocytes might be the result of excessive accumulation of phosphatidylcholine and a reduction of phosphatidic acid. Our findings have uncovered significant roles of PITPNC1 in mitochondrial phospholipid homeostasis and BAT thermogenesis.

Insights into the development of pentylenetetrazole-induced epileptic seizures from dynamic metabolomic changes - Xue Zhao; Peixuan Cheng; Ru Xu; Kaili Meng; Sha Liao; Pu Jia; Xiaohui Zheng; Chaoni Xiao (Metabolic Brain Disease, 2022)

Discovery of the oncogenic MDM2, a direct binding target of berberine and a potential therapeutic, in multiple myeloma - Chuting Li; Ru Su; Xiuyuan Wang; Guiping Huang; Yanjun Liu; Juhua Yang; Zhao Yin; Chunming Gu; Jia Fei (Functional & Integrative Genomics, 2022)

Rapid Effect of Enriched Nitrogen on Soybean Nitrogen Uptake, Distribution, and Assimilation During Early Flowering Stage - Hongli Zhou; Qiang Zhao; Ru He; Wei Zhang; Huijun Zhang; Haiying Wang; Xue Ao; Xingdong Yao; Futi Xie (Journal of Soil Science and Plant Nutrition, 2022)

Age, Growth and Population Structure Analyses of the Purpleback Flying Squid Sthenoteuthis oualaniensis in the Northwest Indian Ocean by Beak Microstructure - Hua-Jie Lu; Yu-Zhe Ou; Jing-Ru He; Mao-Lin Zhao; Zi-Yue Chen; Xin-Jun Chen (Journal of Marine Science and Engineering, 2022)
To explore the feasibility of using beak microstructure information to estimate the age of Sthenoteuthis oualaniensis, the microstructures of the upper beaks of individual squid were applied in this work to analyze the ages and growth patterns of squid caught from February–May 2019 and from October–December 2020 in the northwest Indian Ocean. The results indicated that the squid samples in the two years were no older than 9 months, and the samples in 2019 were autumn population and 2020 were spring population. The linear growth model of the autumn population (2019) was the best model for describing the relationship between age and ML, while the power model of the spring population (2020) was the best for describing the relationship between age and ML. The maximum instantaneous growth rate (IGR) and absolute daily growth rate (AGR) values of the spring population were 0.24%/d and 1.09 mm/d, respectively, occurring in squid between 200 and 220 days of age. The maximum IGR and AGR values of the autumn population were 0.69%/d and 1.73 mm/d, respectively, occurring in squid between 200 and 240 days of age. The period from 141–260 days (5–8 months) was considered to correspond to the subadult stage in the whole life history of S. oualaniensis in the Northwest Indian Ocean. The beak microstructure information can be effectively applied to estimate the age of S. oualaniensis individuals.

Impacts of nanoplastics on life-history traits of marine rotifer (Brachionus plicatilis) are recovered after being transferred to clean seawater - Dong Wang; Shaoguo Ru; Wei Zhang; Zhenzhong Zhang; Yuejiao Li; Lingchao Zhao; Lianxu Li; Jun Wang (Environmental Science and Pollution Research, 2022)

Whole Genome Sequencing and Biological Characteristics of Two Strains of Porcine Escherichia coli Isolated from Saba Pigs - Bo Zhang; Weiwei Zhao; Bin Gao; Chunlan Shan; Xi Wang; Quan Wan; Jing Deng; Jinglong Cha; Bingxun Chen; Dongmei Han; Libo Gao; Pingxing Ao; et al. (Current Microbiology, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

First report of Capsicum frutescens endornavirus 1 infecting pepper in China - Ming-xia Gong; Hu Zhao; Xing Wu; Meng Wang; Zeng-jing Zhao; Zhi He; Ru-kui Huang; Jing-ping Sun; Ri-sheng Wang (Journal of Plant Pathology, 2022)

Land development suitability analysis for transport planning evaluation and optimization in mountainous ecological region - Gao-ru Zhu; Man Wang; Qi-li Li; Jie Liu; Yan-ni Zhao; Jia-wei Gao; Hong-lei Xu (Journal of Mountain Science, 2022)

NNMT is induced dynamically during beige adipogenesis in adipose tissues depot-specific manner - Ru Jia; Xiaojing Wei; Jianan Jiang; Zhao Yang; Jiaqi Huang; Jing Liu; Jianqun Yan; Xiao Luo (Journal of Physiology and Biochemistry, 2022)

Succinic acid inhibits photosynthesis of Microcystis aeruginosa via damaging PSII oxygen-evolving complex and reaction center - Yi-dong Chen; Yuan Zhu; Jian-pan Xin; Chu Zhao; Ru-nan Tian (Environmental Science and Pollution Research, 2021)

Taxonomic description of Pseudomonas rhizovicinus sp. nov., isolated from the rhizosphere of a desert shrub Haloxylon ammodendron - Ao-Lei He; Hui-Ru Li; Hui-Ping Li; Jing-Yi Gou; Jia Chen; Qi Zhao; Jin-Lin Zhang (Antonie van Leeuwenhoek, 2021)

Emerging Role of PD-1 in the Central Nervous System and Brain Diseases - Junli Zhao; Alexus Roberts; Zilong Wang; Justin Savage; Ru-Rong Ji (Neuroscience Bulletin, 2021)

LncRNA TUG1 exhibits pro-fibrosis activity in hypertrophic scar through TAK1/YAP/TAZ pathway via miR-27b-3p - Xian-Min Li; Wen-Yuan Yu; Qi Chen; Hui-Ru Zhuang; Su-Yue Gao; Tian-Lan Zhao (Molecular and Cellular Biochemistry, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Present in-situ stress distribution characteristics of strike-slip in SH Oilfield, Tarim Basin - Teng Zhao; Wenge Hu; Rui Zhao; Min Yang; Qiang Wang; Huixi Lin; Zhixing Ru; Dian Bao; Fei Cao (Arabian Journal of Geosciences, 2021)

Luteolin alleviates ulcerative colitis through SHP-1/STAT3 pathway - Bo-Lin Li; Dan-Yang Zhao; Peng-Li Du; Xiao-Tian Wang; Qian Yang; Yan-Ru Cai (Inflammation Research, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Genetic Analysis of Prosaposin, the Lysosomal Storage Disorder Gene in Parkinson’s Disease - Yong-Ping Chen; Xiao-Jing Gu; Ru-Wei Ou; Ling-Yu Zhang; Yan-Bing Hou; Kun-Cheng Liu; Bei Cao; Qian-Qian Wei; Wei Song; Bi Zhao; Ying Wu; Jing-Qiu Cheng; et al. (Molecular Neurobiology, 2021)

Haplotype networks of Phycocalidia tanegashimensis (Bangiales, Rhodophyta) indicate a probable invasion from the South China Sea to Brazil - Wan Zhao; Lei Dong; Dang Diem Hong; Juliet Brodie; Wei-Zhou Chen; Dam Duc Tien; Wei Zhou; Qin-Qin Lu; Mei-Ru Zhang; Li-En Yang (Marine Biodiversity, 2021)

A study on the reservoir controlling characteristics and mechanism of the strike slip faults in the northern slope of Tazhong uplift, Tarim Basin, China - Zhongpei Zhang; Yuan Kang; Huixi Lin; Jun Han; Rui Zhao; Xiuxiang Zhu; Zhixing Ru; Chongyang Xiao (Arabian Journal of Geosciences, 2021)

Evaluation and application of conductivity of strike slip faults in China Shunbei reservoir, Tarim Basin - Wenge Hu; Qiang Wang; Rui Zhao; Zhixing Ru (Arabian Journal of Geosciences, 2021)

FOXG1 Directly Suppresses Wnt5a During the Development of the Hippocampus - Yang Ni; Bin Liu; Xiaojing Wu; Junhua Liu; Ru Ba; Chunjie Zhao (Neuroscience Bulletin, 2021)

Alkaloids and phenylpropanoid from Rhizomes of Arundo donax L - Qing-Ru Liu; Juan Li; Xiao-Fang Zhao; Bo Xu; Xing-Hua Xiao; Jie Ren; Shun-Xiang Li (Natural Product Research, 2021)

TRIP13 promotes the proliferation and invasion of lung cancer cells via the Wnt signaling pathway and epithelial–mesenchymal transition - Zhi-Han Li; Lei Lei; Liang-Ru Fei; Wen-Jing Huang; Yi-Wen Zheng; Mai-Qing Yang; Zhao Wang; Chen-Chen Liu; Hong-Tao Xu (Journal of Molecular Histology, 2021)

A new cyclic peptide from the fibrous root of Pseudostellaria heterophylla - Xiao-fei Zhao; Qian Zhang; Han-tao Zhao; Yan-da Zhang; Han-ru Liu; Lu-jiang Yuan; Qian-feng Chen (Natural Product Research, 2020)

Correction to: Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Chang-Qi Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Functional connectivity changes of nucleus Accumbens Shell portion in left mesial temporal lobe epilepsy patients - Ru Yang; Xixi Zhao; Jun Liu; Xufeng Yao; Feng Hou; Yikai Xu; Qianjin Feng (Brain Imaging and Behavior, 2020)

FW0622, a new siderophore isolated from marine Verrucosispora sp. by genomic mining - Wei Zhao; Fei Peng; Chuan-xi Wang; Yang Xie; Ru Lin; Zhi-kai Fang; Fei Sun; Yun-yang Lian; Hong Jiang (Natural Product Research, 2020)

Elevated ROS depress mitochondrial oxygen utilization efficiency in cardiomyocytes during acute hypoxia - Ru-Zhou Zhao; Xiao-Bo Wang; Shuai Jiang; Ning-Yu Ru; Bo Jiao; Yun-Ying Wang; Zhi-Bin Yu (Pflügers Archiv - European Journal of Physiology, 2020)

Novel ACADVL variants resulting in mitochondrial defects in long-chain acyl-CoA dehydrogenase deficiency - Ting Chen; Fan Tong; Xiao-yu Wu; Ling Zhu; Qiu-zi Yi; Jing Zheng; Ru-lai Yang; Zheng-yan Zhao; Xiao-hui Cang; Qiang Shu; Ping-ping Jiang (Journal of Zhejiang University-SCIENCE B, 2020)

Cadmium phytotoxicity, related physiological changes in Pontederia cordata: antioxidative, osmoregulatory substances, phytochelatins, photosynthesis, and chlorophyll fluorescence - Jian-pan Xin; SiSi Ma; Chu Zhao; Yan Li; Ru-nan Tian (Environmental Science and Pollution Research, 2020)

Emerging relationship between RNA helicases and autophagy - Miao-miao Zhao; Ru-sha Wang; Yan-lin Zhou; Zheng-gang Yang (Journal of Zhejiang University-SCIENCE B, 2020)

Multiplex RT–PCR Assay for the Simultaneous Detection and Identification of Five Sugarcane Viruses - Xiao-Yan Feng; Wen-Zhi Wang; Lin-Bo Shen; Jun-Gang Wang; Guo-Ru Xiong; Cui-Lian Feng; Ting-Ting Zhao; Shu-Zhen Zhang (Sugar Tech, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Prenatal di-(2-ethylhexyl) phthalate maternal exposure impairs the spatial memory of adult mouse offspring in a phase- and gender-dependent manner - Ling-Li Zhao; Ru Shen; Cong-Cong Sun; Shan-Yu Zhang; Bo Wang; Mei-Fang Sun; De-Xiang Xu (Environmental Science and Pollution Research, 2020)

Thioredoxin-Interacting Protein (TXNIP) Regulates Parkin/PINK1-mediated Mitophagy in Dopaminergic Neurons Under High-glucose Conditions: Implications for Molecular Links Between Parkinson’s Disease and Diabetes - Cun-Jin Su; Zhu Shen; Ru-Xiao Cui; Ya Huang; De-Lai Xu; Feng-Lun Zhao; Jie Pan; Ai-Ming Shi; Tong Liu; Yun-Li Yu (Neuroscience Bulletin, 2020)

Applying multivariate statistics for identification of groundwater chemistry and qualities in the Sugan Lake Basin, Northern Qinghai-Tibet Plateau, China - Juan Xiang; Jun-ju Zhou; Jun-cang Yang; Mei-hua Huang; Wei Feng; Qiao-qiao Li; Dong-xiang Xue; Ya-ru Zhao; Guo-feng Zhu (Journal of Mountain Science, 2020)

Modified stepwise mini-incision microdissection testicular sperm extraction: a useful technique for patients with a history of orchidopexy affected by non-obstructive azoospermia - Peng Li; Chen-cheng Yao; Er-lei Zhi; Yuan Xu; Zhong Wan; Ying-chuan Jiang; Yu-hua Huang; Yue-hua Gong; Hui-xing Chen; Ru-hui Tian; Chao Yang; Liang-yu Zhao; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

Probabilistic evaluation of drilling rate index based on a least square support vector machine and Monte Carlo simulation - Zhongliang Ru; Hongbo Zhao; Changxing Zhu (Bulletin of Engineering Geology and the Environment, 2019)

Overview of pharmacological activities of Andrographis paniculata and its major compound andrographolide - Yan Dai; Shao-Ru Chen; Ling Chai; Jing Zhao; Yitao Wang; Ying Wang (Critical Reviews in Food Science and Nutrition, 2019)

The transcription factor MYB15 is essential for basal immunity (PTI) in Chinese wild grape - Yangyang Luo; Ru Bai; Jing Li; Weidong Yang; Ruixiang Li; Qingyang Wang; Guifang Zhao; Dong Duan (Planta, 2019)

The complete chloroplast genome of Calycanthus chinensis, an endangered species endemic to China - Xiaodan Chen; Jia Yang; Hao Zhang; Ru Bai; Xiao Zhang; Guoqing Bai; Panfeng Dai; Guifang Zhao (Conservation Genetics Resources, 2019)

Detecting and attributing vegetation changes in Taihang Mountain, China - Shi Hu; Fei-yu Wang; Che-sheng Zhan; Ru-xin Zhao; Xiong-guo Mo; Liang-mei-zi Liu (Journal of Mountain Science, 2019)

A specific allele of MYB14 in grapevine correlates with high stilbene inducibility triggered by Al3+ and UV-C radiation - Ru Bai; Yangyang Luo; Lixin Wang; Jing Li; Kerun Wu; Guifang Zhao; Dong Duan (Plant Cell Reports, 2019)

Transplantation of UC-MSCs on collagen scaffold activates follicles in dormant ovaries of POF patients with long history of infertility - Lijun Ding; Guijun Yan; Bin Wang; Lu Xu; Yan Gu; Tong Ru; Xiaoying Cui; Lei Lei; Jingyu Liu; Xiaoqiang Sheng; Bin Wang; Chunxue Zhang; et al. (Science China Life Sciences, 2018)

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

Chloroplast genome sequence of an endangered non-photosynthetic mycoheterotrophic species Monotropastrum sciaphilum (Andres) G. D. Wallace - Qian-Ru Zhao; Zhen-Wen Liu; Chao Shi; Hua Peng; Shu-Gang Lu (Conservation Genetics Resources, 2018)

Low pH stress responsive transcriptome of seedling roots in wheat (Triticum aestivum L.) - Haiyan Hu; Jie He; Junjie Zhao; Xingqi Ou; Hongmin Li; Zhengang Ru (Genes & Genomics, 2018)

Subdivision and age of the Yanchang Formation and the Middle/Upper Triassic boundary in Ordos Basin, North China - Shenghui Deng; Yuanzheng Lu; Zhong Luo; Ru Fan; Xin Li; Yi Zhao; Xueying Ma; Rukai Zhu; Jingwei Cui (Science China Earth Sciences, 2018)

Cyproheptadine Regulates Pyramidal Neuron Excitability in Mouse Medial Prefrontal Cortex - Yan-Lin He; Kai Wang; Qian-Ru Zhao; Yan-Ai Mei (Neuroscience Bulletin, 2018)

Turning Death to Growth: Hematopoietic Growth Factors Promote Neurite Outgrowth through MEK/ERK/p53 Pathway - Mei Gao; Li-Ru Zhao (Molecular Neurobiology, 2018)

Sexual characteristics of male guppies Poecilia reticulata serve as effect biomarkers of estrogens - Hua Tian; Yun Li; Wei Wang; Fei Zhao; Su Gao; Shaoguo Ru (Journal of Oceanology and Limnology, 2018)

Investigating the composition characteristics of dissolved and particulate/colloidal organic matter in effluent-dominated stream using fluorescence spectroscopy combined with multivariable analysis - Min-Da Yu; Xiao-Song He; Bei-Dou Xi; Ru-Tai Gao; Xian-Wei Zhao; Hui Zhang; Cai-Hong Huang; Wenbing Tan (Environmental Science and Pollution Research, 2018)

Over-expression of the Arabidopsis formate dehydrogenase in chloroplasts enhances formaldehyde uptake and metabolism in transgenic tobacco leaves - Ru Wang; Zhidong Zeng; Hongxia Guo; Hao Tan; Ang Liu; Yan Zhao; Limei Chen (Planta, 2018)

Analysis of three-dimensional endocardial and epicardial strains from cardiac magnetic resonance in healthy subjects and patients with hypertrophic cardiomyopathy - Xiaodan Zhao; Ru San Tan; Hak Chiaw Tang; Shuang Leng; Jun-Mei Zhang; Liang Zhong (Medical & Biological Engineering & Computing, 2018)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Retraction Note To: VEGF Silencing Inhibits Human Osteosarcoma Angiogenesis and Promotes Cell Apoptosis via PI3K/AKT Signaling Pathway - Jian Zhao; Zi-Ru Zhang; Na Zhao; Bao-An Ma; Qing-Yu Fan (Cell Biochemistry and Biophysics, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

Transplantation of collagen scaffold with autologous bone marrow mononuclear cells promotes functional endometrium reconstruction via downregulating ΔNp63 expression in Asherman’s syndrome - Guangfeng Zhao; Yun Cao; Xianghong Zhu; Xiaoqiu Tang; Lijun Ding; Haixiang Sun; Juan Li; Xinan Li; Chenyan Dai; Tong Ru; Hui Zhu; Jingjie Lu; et al. (Science China Life Sciences, 2017)

Improved salt tolerance of medicinal plant Codonopsis pilosula by Bacillus amyloliquefaciens GB03 - Qing-Qing Han; Yong-Na Wu; Hui-Juan Gao; Rui Xu; Paul W. Paré; Huazhong Shi; Qi Zhao; Hui-Ru Li; Sardar Ali Khan; Yin-Quan Wang; Suo-Min Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2017)

Three-Dimensional Tricuspid Annular Motion Analysis from Cardiac Magnetic Resonance Feature-Tracking - Shuang Leng; Meng Jiang; Xiao-Dan Zhao; John Carson Allen; Ghassan S. Kassab; Rong-Zhen Ouyang; Ju-Le Tan; Ben He; Ru-San Tan; Liang Zhong (Annals of Biomedical Engineering, 2016)

Reactive Oxygen Species-mediated Loss of Phenotype of Parvalbumin Interneurons Contributes to Long-term Cognitive Impairments After Repeated Neonatal Ketamine Exposures - Hui Zhang; Xiao-ru Sun; Jing Wang; Zhen-zhen Zhang; Hong-ting Zhao; Hui-hui Li; Mu-huo Ji; Kuan-yu Li; Jian-jun Yang (Neurotoxicity Research, 2016)

Norovirus outbreaks in Fengtai District, Beijing, China, 2014 - Jin-Song Li; Meng Qin; Xiao-Gen Dong; Jun-Yong Yang; Xiao-Xin Yang; Xiu-xia Wei; Zhao-e Wang; Hui-ru Feng; Qin-rui Wu; Ruo-xi Li; Jie Li; Zhao-Jun Duan (Archives of Virology, 2016)

Dietary lipid concentrations influence growth, liver oxidative stress, and serum metabolites of juvenile hybrid snakehead (Channa argus × Channa maculata) - Peng-Fei Zhao; Fa-Jian Li; Xiao-Ru Chen; Yong-Jun Chen; Shi-Mei Lin; Lu Zhang; Yun Li (Aquaculture International, 2016)

A Waterborne Gastroenteritis Outbreak Caused by Norovirus GII.17 in a Hotel, Hebei, China, December 2014 - Meng Qin; Xiao-Gen Dong; Yan-Yan Jing; Xiu-xia Wei; Zhao-E Wang; Hui-Ru Feng; Hong Yu; Jin-Song Li; Jie Li (Food and Environmental Virology, 2016)

Adsorption of Cd(II) by two variable-charge soils in the presence of pectin - Ru-hai Wang; Xiao-fang Zhu; Wei Qian; Min-hua Zhao; Ren-kou Xu; Yuan-chun Yu (Environmental Science and Pollution Research, 2016)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Fast Marching and Runge–Kutta Based Method for Centreline Extraction of Right Coronary Artery in Human Patients - Hengfei Cui; Desheng Wang; Min Wan; Jun-Mei Zhang; Xiaodan Zhao; Ru San Tan; Weimin Huang; Wei Xiong; Yuping Duan; Jiayin Zhou; Tong Luo; Ghassan S. Kassab; et al. (Cardiovascular Engineering and Technology, 2016)

Pertrogenesis and tectonic implications of the late Jurassic basic rocks from the northern Shi‐Hang zone, Southeast China - Qing Zhou; Yao–hui Jiang; Shi–yong Liao; Peng Zhao; Ru–ya Jia; Zheng Liu; Guo–chang Wang; Chun–yu Ni (Island Arc, 2016)
The tectonic setting of the late mesozoic of South China is in a debate between two schools of thought: an intra‐continental rift zone along a passive continental margin or active rifting associated with subduction of the paleo‐Pacific Plate. In this study, we present new sensitive high‐resolution ion microprobe (SHRIMP) U‐Pb zircon ages, along with geochemical data of three basic dikes that cross‐cut the Dexing porphyry copper deposit. The deposit is the largest of its kind in eastern China and part of large scale mineralization associated with Mesozoic magmatic activity in the area. Our results indicate that the dikes were emplaced in the Late Jurassic with an average U‐Pb age of 153.5 ± 2.4 Ma. The intrusions have bulk ε Nd (t) of ca +0.7 and zircon ε Hf (t) value of +1.54 to +6.92. Based on relatively enriched light rare earth elements (LREE) and depleted high‐field‐strength elements (HFSE) abundances with pronounced negative Ta–Nb, Hf–Zr and Ti anomalies in multi‐element diagrams, we propose that these dikes were derived from a subduction‐modified lithospheric mantle source. The variability in Hf isotopes identifies some degree of crustal contaminations. Our data support a scenario with a back‐arc extensional setting or an intra‐arc rift environment associated with the westward subduction of the paleo‐Pacific Plate at or prior to the late Jurassic as the most likely cause for these subduction signatures.

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Sodium Channel Voltage-Gated Beta 2 Plays a Vital Role in Brain Aging Associated with Synaptic Plasticity and Expression of COX5A and FGF-2 - Yan-Bin XiYang; You-Cui Wang; Ya Zhao; Jin Ru; Bing-Tuan Lu; Yue-Ning Zhang; Nai-Chao Wang; Wei-Yan Hu; Jia Liu; Jin-Wei Yang; Zhao-Jun Wang; Chun-Guang Hao; et al. (Molecular Neurobiology, 2016)

Di-(2-ethylhexyl) phthalate accelerates atherosclerosis in apolipoprotein E-deficient mice - Jin-Feng Zhao; Sheng-Huang Hsiao; Ming-Hua Hsu; Kuan-Chuan Pao; Yu Ru Kou; Song-Kun Shyue; Tzong-Shyuan Lee (Archives of Toxicology, 2016)

Identification of geranylgeranyl diphosphate synthase genes from Tripterygium wilfordii - Meng Zhang; Ping Su; Yong-Jin Zhou; Xiu-Juan Wang; Yu-Jun Zhao; Yu-Jia Liu; Yu-Ru Tong; Tian-Yuan Hu; Lu-Qi Huang; Wei Gao (Plant Cell Reports, 2015)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

RETRACTED ARTICLE: VEGF Silencing Inhibits Human Osteosarcoma Angiogenesis and Promotes Cell Apoptosis via PI3K/AKT Signaling Pathway - Jian Zhao; Zi-Ru Zhang; Na Zhao; Bao-An Ma; Qing-Yu Fan (Cell Biochemistry and Biophysics, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Investigation on time-dependent behaviour and long-term stability of underground water-sealed cavern - Huan-ling Wang; Wei-ya Xu; Long Yan; Qing-xiang Meng; Ru-bin Wang; Hai-bin Zhao; Wei-chau Xie (European Journal of Environmental and Civil Engineering, 2015)

Induction of DNA base damage and strand breaks in peripheral erythrocytes and the underlying mechanism in goldfish (Carassius auratus) exposed to monocrotophos - Fei Zhao; Bai Wang; Xiaona Zhang; Hua Tian; Wei Wang; Shaoguo Ru (Fish Physiology and Biochemistry, 2015)

A Practical Indirect Back Analysis Approach for Geomechanical Parameters Identification - Hongbo Zhao; Zhongliang Ru; Shunde Yin (Marine Georesources & Geotechnology, 2015)

Ameliorative effects of Bacillus subtilis ANSB01G on zearalenone toxicosis in pre-pubertal female gilts - Lihong Zhao; Yuanpei Lei; Yinghui Bao; Ru Jia; Qiugang Ma; Jianyun Zhang; Jun Chen; Cheng Ji (Food Additives & Contaminants: Part A, 2015)

Influence of pH, inorganic anions, and dissolved organic matter on the photolysis of antimicrobial triclocarban in aqueous systems under simulated sunlight irradiation - Shi-Ling Ding; Xi-Kui Wang; Wen-Qiang Jiang; Ru-Song Zhao; Ting-Ting Shen; Chen Wang; Xia Wang (Environmental Science and Pollution Research, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Genetic analysis and chromosome mapping of a thermo-sensitive genic male sterile gene in wheat - Zhen-Gang Ru; Li-Ping Zhang; Tie-Zhu Hu; Hong-Yu Liu; Qing-Kai Yang; Man-Li Weng; Bin Wang; Chang-Ping Zhao (Euphytica, 2015)

A study of shear strength properties of municipal solid waste in Chongqing landfill, China - Yan Ru Zhao; Qiang Xie; Gui Lin Wang; Yong Jian Zhang; Yong Xing Zhang; Wenjun Su (Environmental Science and Pollution Research, 2014)

Cloning and characterisation of a pepper aquaporin, CaAQP, which reduces chilling stress in transgenic tobacco plants - Yan-Xu Yin; Wei-Li Guo; Ying-Li Zhang; Jiao-Jiao Ji; Huai-Juan Xiao; Fei Yan; Yan-Yan Zhao; Wen-Chao Zhu; Ru-Gang Chen; Wei-Guo Chai; Zhen-Hui Gong (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Structure–activity relationships of anthocyanidin glycosylation - Chang Ling Zhao; Zhong Jian Chen; Xue Song Bai; Can Ding; Ting Ju Long; Fu Gang Wei; Kang Ru Miao (Molecular Diversity, 2014)

Occurrence, sources, and ecological risks of PBDEs, PCBs, OCPs, and PAHs in surface sediments of the Yangtze River Delta city cluster, China - Ting Zhang; Wen-Long Yang; She-Jun Chen; Dian-Long Shi; Hu Zhao; Yi Ding; Ye-Ru Huang; Nan Li; Yue Ren; Bi-Xian Mai (Environmental Monitoring and Assessment, 2014)

Effect of copper-induced oxidative stress on sclerotial differentiation and antioxidant properties of Penicillium thomii PT95 strain - Ze-Qing Zhang; Wen-Jing Zhao; Dan-Dan Long; Lin-Ru Niu; Jian-Rong Han (World Journal of Microbiology and Biotechnology, 2014)

Comparison of fatty acid and amino acid profiles of steamed Chinese mitten crab - Yan-Ru Guo; Sai-Qi Gu; Xi-Chang Wang; Lin-Min Zhao; Jin-Yuan Zheng (Fisheries Science, 2014)

SNP and haplotype analysis reveal IGF2 variants associated with growth traits in Chinese Qinchuan cattle - Yong-Zhen Huang; Zhao-Yang Zhan; Xin-Yi Li; Sheng-Ru Wu; Yu-Jia Sun; Jing Xue; Xian-Yong Lan; Chu-Zhao Lei; Chun-Lei Zhang; Yu-Tang Jia; Hong Chen (Molecular Biology Reports, 2014)

Origin of Middle Cambrian and Late Silurian potassic granitoids from the western Kunlun orogen, northwest China: a magmatic response to the Proto-Tethys evolution - Zheng Liu; Yao-Hui Jiang; Ru-Ya Jia; Peng Zhao; Qing Zhou; Guo-Chang Wang; Chun-Yu Ni (Mineralogy and Petrology, 2014)

Origin of Early Cretaceous high-K calc-alkaline granitoids, western Tibet: implications for the evolution of the Tethys in NW China - Yao-Hui Jiang; Zheng Liu; Ru-Ya Jia; Shi-Yong Liao; Peng Zhao; Qing Zhou (International Geology Review, 2014)

Circulating microparticles in patients with coronary heart disease and its correlation with interleukin-6 and C-reactive protein - Ying Cui; Lihui Zheng; Ming Jiang; Ru Jia; Xiao Zhang; Qishan Quan; Guiqin Du; Dongjin Shen; Xiaodan Zhao; Wenying Sun; Hongwei Xu; Lijuan Huang (Molecular Biology Reports, 2013)

Comparison of the dissipation behaviour of three neonicotinoid insecticides in tea - Ru-Yan Hou; Jin-Feng Hu; Xiao-San Qian; Ting Su; Xiao-Hui Wang; Xiu-Xia Zhao; Xiao-Chun Wan (Food Additives & Contaminants: Part A, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Fine structure and primary sensory projections of sensilla located in the labial-palp pit organ of Helicoverpa armigera (Insecta) - Xin-Cheng Zhao; Qing-Bo Tang; Bente G. Berg; Yang Liu; Yan-Ru Wang; Feng-Ming Yan; Gui-Rong Wang (Cell and Tissue Research, 2013)

Petrogenesis and tectonic implications of early Silurian high-K calc-alkaline granites and their potassic microgranular enclaves, western Kunlun orogen, NW Tibetan Plateau - Ru-Ya Jia; Yao-Hui Jiang; Zheng Liu; Peng Zhao; Qing Zhou (International Geology Review, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Protective effect of hydrogen-rich saline on ischemia/reperfusion injury in rat skin flap - Ling Zhao; You-bin Wang; Shi-rui Qin; Xue-mei Ma; Xue-jun Sun; Ming-lian Wang; Ru-gang Zhong (Journal of Zhejiang University-SCIENCE B, 2013)

Photodegradation of the antimicrobial triclocarban in aqueous systems under ultraviolet radiation - Shi-Ling Ding; Xi-Kui Wang; Wen-Qiang Jiang; Xia Meng; Ru-Song Zhao; Chen Wang; Xia Wang (Environmental Science and Pollution Research, 2013)

Imposex effects on the veined rapa whelk (Rapana venosa) in Bohai Bay, China - Li-hui An; Yanqiang Zhang; Shuang-shuang Song; Yue Liu; Zi-cheng Li; Hao Chen; Xing-ru Zhao; Kun Lei; Junmin Gao; Bing-hui Zheng (Ecotoxicology, 2013)

Mantle origin of the Dexing porphyry copper deposit, SE China - Qing Zhou; Yao-Hui Jiang; Hui-Hua Zhang; Shi-Yong Liao; Guo-Dong Jin; Peng Zhao; Ru-Ya Jia; Zheng Liu (International Geology Review, 2013)

Mutations in AP22.65 accelerate flowering in Arabidopsis thaliana - Ji Hong Xing; Feng Ru Wang; Jiao Jia; Jing Zhang; Li Li; Zhan Chen; Qiao Yun Weng; Ping Yang; Ye Zhang; Bin Zhao; He Long Si; Jin Gao Dong; et al. (Journal of Plant Biology, 2013)

Slope reliability analysis by updated support vector machine and Monte Carlo simulation - Shaojun Li; Hong-Bo Zhao; Zhongliang Ru (Natural Hazards, 2013)

Effects of recombinant hIL-2-Luffin P1 immunotoxin combining with arotinoid ethylester on the proliferation and apoptosis of Hut-78 cells - Shu-lei Liu; Wei He; Ru-peng Wang; Zhi Li; Ju Wu; Yun Zhao; Xiao-hong Hu (Molecular & Cellular Toxicology, 2012)

Cloning and sequence analysis of chitin synthase gene fragments of Demodex mites - Ya-e Zhao; Zheng-hang Wang; Yang Xu; Ji-ru Xu; Wen-yan Liu; Meng Wei; Chu-ying Wang (Journal of Zhejiang University-SCIENCE B, 2012)

The mitochondrial genome of the quiet-calling katydids, Xizicus fascipes (Orthoptera: Tettigoniidae: Meconematinae) - MING RU YANG; ZHI JUN ZHOU; YAN LIN CHANG; LE HONG ZHAO (Journal of Genetics, 2012)

Lead and cadmium-induced oxidative stress impacting mycelial growth of Oudemansiella radicata in liquid medium alleviated by microbial siderophores - Yan-ru Cao; Xi-yu Zhang; Jia-yu Deng; Qi-qi Zhao; Heng Xu (World Journal of Microbiology and Biotechnology, 2012)

Cutaneous Protothecosis in Patient with Diabetes Mellitus and Review of Published Case Reports - Qiang-Qiang Zhang; Li Li; Li-Ping Zhu; Ying Zhao; Yun-Ru Wang; Jun-hao Zhu; Min Zhu (Mycopathologia, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Sociodemographic characteristics and risk factor analysis of Demodex infestation (Acari: Demodicidae) - Ya-e Zhao; Na Guo; Meng Xun; Ji-ru Xu; Mei Wang; Duo-lao Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Antioxidant effect of a phytoestrogen equol on cultured muscle cells of embryonic broilers - Xiao-Jing Wei; Jing Wu; Ying-Dong Ni; Li-Zhi Lu; Ru-Qian Zhao (In Vitro Cellular & Developmental Biology - Animal, 2011)

Infrasound Exposure Induces Apoptosis of Rat Cardiac Myocytes by Regulating the Expression of Apoptosis-Related Proteins - Zhao-Hui Pei; Bao-Ying Chen; Ru Tie; Hai-Feng Zhang; Ge Zhao; Ping Qu; Xiao-Xing Zhu; Miao-Zhang Zhu; Jun Yu (Cardiovascular Toxicology, 2011)

Studies on hemolysis of hemolysin produced by Synechocystis sp. PCC 6803 - Shuai Bi; Wei Wang; Yuanyuan Zhao; Shaoguo Ru; Yunzhang Liu (Journal of Ocean University of China, 2011)

Colonization of the Tibetan Plateau by the homoploid hybrid pine Pinus densata - BAOSHENG WANG; JIAN‐FENG MAO; JIE GAO; WEI ZHAO; XIAO‐RU WANG (Molecular Ecology, 2011)
Pinus densata is an intriguingly successful homoploid hybrid species that occupies vast areas of the southeastern Tibetan Plateau in which neither of its parental species are present, but the colonization processes involved are poorly understood. To shed light on how this species colonized and became established on the plateau, we surveyed paternally inherited chloroplast (cp) and maternally inherited mitochondrial (mt) DNA variation within and among 54 populations of P. densata and its putative parental species throughout their respective ranges. Strong spatial genetic structure of both cp and mtDNA were detected in P. densata populations. Mitotypes specific to P. densata were likely generated by complex recombination events. A putative ancestral hybrid zone in the northeastern periphery of P. densata was identified, and we propose that the species then colonized the plateau by migrating westwards. Along the colonization route, consecutive bottlenecks and surfing of rare alleles caused a significant reduction in genetic diversity and strong population differentiation. The direction and intensity of introgression from parental species varied among geographic regions. In western parts of its range, the species seems to have been isolated from seed and pollen flow from its parent species for a long time. The observed spatial distribution of genetic diversity in P. densata also appears to reflect the persistence of this species on the plateau during the last glaciation. Our results indicate that both ancient and contemporary population dynamics have contributed to the spatial distribution of genetic diversity in P. densata , which accordingly reflects its evolutionary history.

Effect of glucocorticoids pretreatment on steroidogenic capacity of adrenocortical cells isolated from Meishan piglets - Liu-An Li; Zhan-Wang Wu; Xiao-Jing Yang; Ying-Dong Ni; Nahid Parvizi; Ru-Qian Zhao (In Vitro Cellular & Developmental Biology - Animal, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

Simultaneous Expression of Spinacia oleracea Chloroplast Choline Monooxygenase (CMO) and Betaine Aldehyde Dehydrogenase (BADH) Genes Contribute to Dwarfism in Transgenic Lolium perenne - Yongxia Bao; Ru Zhao; Feifei Li; Wei Tang; Liebao Han (Plant Molecular Biology Reporter, 2011)

Effect of neuronal excitotoxicity on Munc18-1 distribution in nuclei of rat hippocampal neuron and primary cultured neuron - Yan-Ping Zhang; Ping Wan; Hong-Quan Wang; Hong Zhao; Yu-Xia Xu; Ru Yang; Cui-Qing Zhu (Neuroscience Bulletin, 2011)

Asialoglycoprotein receptor interacts with the preS1 domain of hepatitis B virus in vivo and in vitro - Xi Zhang; Shu-mei Lin; Tian-yan Chen; Min Liu; Feng Ye; Yun-ru Chen; Lei Shi; Ying-li He; Lie-xiu Wu; Shu-qin Zheng; Ying-ren Zhao; Shu-lin Zhang (Archives of Virology, 2011)

Establishment of a transgene expression system for the marine microalga Schizochytrium by 18S rDNA-targeted homologous recombination - Ru-Bin Cheng; Xiang-Zhi Lin; Zhao-Kai Wang; Shan-Jun Yang; Hui Rong; Yong Ma (World Journal of Microbiology and Biotechnology, 2011)

PTEN status is related to cell proliferation and self-renewal independent of CD133 phenotype in the glioma-initiating cells - Ru-Bin Cheng; Rui-Juan Ma; Zhao-Kai Wang; Shan-Jun Yang; Xiang-Zhi Lin; Hui Rong; Yong Ma (Molecular and Cellular Biochemistry, 2011)

Comparison of Non-covalent Interactions Between a Series of N-Phosphoryl Dipeptide or Methyl Esters and Protein by Electrospray Ionization Mass Spectrometry - Li-ming Qiang; Ming-xiu Lü; Xu-ru Dong; Shu-xia Cao; Kui Lu; Yu-fen Zhao (International Journal of Peptide Research and Therapeutics, 2011)

Special Distribution of Polybrominated Diphenyl Ethers in Brain Tissues of Free-range Domestic Hens and Ducks from a Village near an Electronic Waste Recycling Site in South China - Zhong-Zhi Yang; Yong-Fang Li; Shan Fu; Xing-Ru Zhao (Bulletin of Environmental Contamination and Toxicology, 2011)

Genetic Analysis and Molecular Mapping of a Novel Gene Conferring Resistance to Rice Stripe Virus - Feng Zhao; Zhijun Cai; Tiezhu Hu; Haigen Yao; Li Wang; Na Dong; Bin Wang; Zhengang Ru; Wenxue Zhai (Plant Molecular Biology Reporter, 2010)

A Series of Novel Rare Earth Molybdotungstosilicate Heteropolyoxometalates Binding to Bovine Serum Albumin: Spectroscopic Approach - Yan-Jun Hu; Yu Ou-Yang; Ai-Min Bai; Ru-Ming Zhao; Yi Liu (Biological Trace Element Research, 2010)

Biological Activation of Heteropoly Complex of Molybdotungstosilicate Containing Lanthanum K10H3La(SiMo6W5O39)2⋅26H2O: Spectroscopic Approach and Microcalorimetry - Yan-Jun Hu; Yu Ou-Yang; Ru-Ming Zhao; Yi Liu (Biological Trace Element Research, 2010)

Segmentation of multispectral high-resolution satellite imagery using log Gabor filters - Pengfeng Xiao; Xuezhi Feng; Ru An; Shuhe Zhao (International Journal of Remote Sensing, 2010)

Genetic Diversity and Population Structure of Celosia argentea and Related Species Revealed by SRAP - Na Feng; Qie Xue; Qinghua Guo; Ru Zhao; Meili Guo (Biochemical Genetics, 2009)

Phthalic Acid Induces Oxidative Stress and Alters the Activity of Some Antioxidant Enzymes in Roots of Malus prunifolia - Ru Bai; Fengwang Ma; Dong Liang; Xin Zhao (Journal of Chemical Ecology, 2009)

Evidence for the production of a proteinaceous hemolytic exotoxin by wild-type strain of Synechocystis sp. PCC 6803 (Cyanobacteria) - Yunzhang Liu; Wei Wang; Shaoguo Ru; Yuanyuan Zhao (Journal of Applied Phycology, 2008)

Treatment and follow-up of children with transient congenital hypothyroidism - Ru-lai Yang; Zhi-wei Zhu; Xue-lian Zhou; Zheng-yan Zhao (Journal of Zhejiang University-SCIENCE B, 2005)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

Habitat Degradation of Rhinopithecus bieti in Yunnan, China - Wen Xiao; Wei Ding; Liang-Wei Cui; Ru-Liang Zhou; Qi-Kun Zhao (International Journal of Primatology, 2003)

A global survey of haplotype frequencies and linkage disequilibrium at the DRD2 locus - Kenneth K. Kidd; Bharti Morar; Carmela M. Castiglione; Hongyu Zhao; Andrew J. Pakstis; William C. Speed; Batsheva Bonne-Tamir; Ru-Band Lu; David Goldman; Chaeyoung Lee; Yong Suk Nam; David K. Grandy; et al. (Human Genetics, 1998)